Energy storage unit, composite fiber energy storage device and preparation method and application of composite fiber energy storage device
The multi-layer fiber woven energy storage unit addresses the structural instability and safety concerns of existing energy storage devices by using woven electrodes and a solid electrolyte, enhancing mechanical stability and preventing electrical shorts.
Patent Information
- Application Number
- CN202510229195.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-28
- Publication Date
- 2025-03-28
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Current energy storage devices, such as lithium-ion batteries and supercapacitors, face issues with layer separation and electrical short circuits due to weak interlayer adhesion and structural instability under mechanical stress, leading to safety concerns and reduced lifespan.
A multi-layer fiber woven energy storage unit with an inner and outer woven electrode and a middle separator layer, utilizing woven fibers for enhanced mechanical interlocking and stability, along with a solid electrolyte to prevent electrolyte leakage and electrical shorts.
The solution provides improved structural stability, safety, and extended lifespan by preventing layer separation and electrolyte leakage, while allowing for flexible mechanical deformation and efficient energy storage.
Smart Images

Figure CN119725790A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of energy storage technology, and in particular to an energy storage unit, a composite fiber energy storage device, and a preparation method and application thereof. Background Art
[0002] With the rapid development of wearable electronic devices, smart textiles and portable electronic products, people have an increasing demand for flexible, lightweight, high energy density, safe and reliable energy storage devices. At present, mainstream energy storage devices on the market, such as lithium-ion batteries and supercapacitors, are usually manufactured using a roll-to-roll process. This process mainly involves coating or depositing functional layers such as electrode materials, current collectors, separators and electrolytes on a substrate in sequence, and then assembling the device by winding or stacking. However, this traditional structural design mainly relies on adhesives or interfacial forces between the functional layers, and there are problems such as weak interlayer bonding and poor structural stability. Under mechanical stress such as bending, stretching or twisting, safety hazards such as interlayer separation, electrolyte leakage, and electrode short circuit are prone to occur, which seriously affects the reliability and life of the device. Summary of the invention
[0003] In view of this, the purpose of the present invention is to provide an energy storage unit, a composite fiber energy storage device, and a preparation method and application thereof. The energy storage unit provided by the present invention is based on a multi-layer fiber braided tube structure, with strong bonding strength of each layer, good structural stability, high safety, and long service life.
[0004] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions: The present invention discloses an energy storage unit having a multi-layer fiber braided tube structure, wherein the multi-layer fiber braided tube structure comprises an inner braided electrode, a middle diaphragm layer and an outer braided electrode; The composition of the inner braided electrode includes a first current collector-active electrode composite fiber and a first support material fiber; the inner braided electrode is a positive electrode or an anode; the chemical composition of the first current collector-active electrode composite fiber includes a first current collector fiber and a first electrode active material; The composition of the middle diaphragm layer includes diaphragm material; The outer braided electrode is composed of a second current collector-active electrode composite fiber and a second support material fiber; the chemical composition of the second current collector-active electrode composite fiber includes a second current collector fiber and a second electrode active material; The energy storage unit further includes an electrolyte, wherein the electrolyte includes solid electrolyte fibers or an electrolyte solution; The diaphragm material includes diaphragm material fibers or layered diaphragm materials; the diaphragm material fibers include at least one of Nafion fibers, polyethylene fibers, polyacrylonitrile fibers, polypropylene fibers, polytetrafluoroethylene fibers, polyimide fibers, polyethersulfone fibers, polyurethane fibers and polytetrafluoroethylene-hexafluoropropylene copolymer fibers; the layered diaphragm material includes a ceramic coated diaphragm, an alumina coated diaphragm or a silica coated diaphragm.
[0005] Preferably, when the diaphragm material is diaphragm material fiber, the composition of the middle diaphragm layer also includes third support material fiber and / or electrolyte fiber.
[0006] Preferably, the first current collector fiber and the second current collector fiber independently include at least one of metal fiber, carbon fiber containing metal coating and carbon fiber; The first support material fiber, the second support material fiber and the third support material fiber independently include at least one of polytetrafluoroethylene fiber, polyvinylidene fluoride, polyethylene fiber, polyimide fiber, aramid fiber, glass fiber, carbon fiber, polyetheretherketone fiber, fluororubber fiber and nano-ceramic fiber.
[0007] Preferably, the energy storage unit further includes a protective layer located on the surface of the outer braided electrode.
[0008] Preferably, the energy storage unit includes a metal ion battery, a metal air battery, a flow battery, a supercapacitor, a dry cell, a fuel cell, an all-solid-state battery or a redox flow battery; the metal ion battery includes a lithium ion battery, a sodium ion battery, a magnesium ion battery, an aluminum ion battery or a potassium ion battery.
[0009] The present invention also provides a method for preparing the energy storage unit described in the above technical solution, comprising the following steps: Performing a first weaving on the raw materials for preparing the inner layer braided electrode to obtain the inner layer braided electrode; The raw materials for preparing the middle diaphragm layer are subjected to a second weaving or winding process on the surface of the inner woven electrode to obtain the middle diaphragm layer; The raw materials for preparing the outer braided electrode are subjected to a third weaving process on the surface of the middle diaphragm layer to form an outer braided electrode, thereby obtaining the energy storage unit; When the electrolyte is a solid electrolyte, solid electrolyte fibers are added during the second weaving or winding process; When the electrolyte is an electrolyte solution, the method further includes: placing the multi-layer fiber braided tube obtained by the third weaving in the electrolyte solution for immersion or electrophoretic deposition; or spraying the multi-layer fiber braided tube obtained by the third weaving with the electrolyte solution.
[0010] The present invention also provides a composite fiber energy storage device, having an overall multi-layer braided tube structure composed of n layers of energy storage units, and a protective layer is arranged between adjacent energy storage units; n is an integer not less than 2; the types of the n layers of energy storage units are the same or different; the n layers of energy storage units are connected in series and / or in parallel; the energy storage unit is the energy storage unit described in the above technical scheme or the energy storage unit prepared by the preparation method described in the above technical scheme.
[0011] Preferably, the series connection is the series connection of the second current collector fiber in the upper layer of energy storage unit and the first current collector fiber in the lower layer of energy storage unit; the series connection is a circuit connection; The parallel connection is that the first current collector fibers of the energy storage unit are connected in parallel with the first current collector fibers, and the second current collector fibers are connected in parallel with the second current collector fibers; the parallel connection mode is circuit connection; The dynamic switching of different energy storage modes of the composite fiber energy storage device is regulated by a circuit connection mode; the circuit connection mode includes at least one of a switching switch, a dynamic electrode connector and an electronic control unit; the different energy storage modes include at least one of a high voltage mode, a high power mode and a long endurance mode.
[0012] The present invention also provides a method for preparing the composite fiber energy storage device described in the above technical solution, comprising the following steps: (1) performing a first weaving on the raw materials for preparing the inner layer braided electrode to obtain the inner layer braided electrode; The raw materials for preparing the middle diaphragm layer are subjected to a second weaving or winding process on the surface of the inner woven electrode to obtain the middle diaphragm layer; The raw materials for preparing the outer braided electrode are braided for the third time on the surface of the middle diaphragm layer to form the outer braided electrode to obtain the first layer of energy storage units, and a protective layer is prepared on the surface of the first layer of energy storage units; When the electrolyte is a solid electrolyte, solid electrolyte fibers are added during the second weaving or winding process; When the electrolyte is an electrolyte solution, the method further comprises: placing the multi-layer fiber braided tube obtained by the third weaving in the electrolyte solution for immersion or electrophoretic deposition; or spraying the multi-layer fiber braided tube obtained by the third weaving with the electrolyte solution; (2) Repeat step (1) n-1 times on the surface of the protective layer to obtain the composite fiber energy storage device.
[0013] The present invention also provides the application of the energy storage unit described in the above technical solution, the energy storage unit prepared by the preparation method described in the above technical solution, the composite fiber energy storage device described in the above technical solution, or the composite fiber energy storage device prepared by the preparation method described in the above technical solution in wearable devices, smart textiles or flexible electronics.
[0014] The energy storage unit and its composite fiber energy storage device provided by the present invention both have a multi-layer fiber braided tube structure. The braided structure enables mechanical locking between the functional layers, and the layers are tightly combined. The interlayer bonding force is much higher than the traditional coating, winding or concentric extrusion method, which avoids interlayer separation and material shedding, and has good structural stability. The multi-layer fiber braided tube structure effectively seals the electrolyte to prevent leakage; at the same time, the tight coating of the diaphragm layer prevents direct contact between the electrodes and avoids the risk of short circuit. The energy storage unit and its composite fiber energy storage device have high safety and long service life. The supporting material fiber provides axial and radial strength for the energy storage unit as a whole, improving the structural stability of the energy storage unit. The multi-layer fiber braided tube structure can adapt to complex mechanical deformations, such as bending, twisting and stretching, and has good flexibility, mechanical strength and durability. While maintaining the high performance of the energy storage unit and the composite fiber energy storage device, it significantly improves its safety and extends its service life, and is suitable for application scenarios such as wearable devices.
[0015] By adjusting the composition and structure of the fiber material, the present invention can optimize the electrochemical performance of the energy storage unit and the composite fiber energy storage device, such as improving the specific capacity, specific power and cycle stability, and can meet the application requirements of different scenarios.
[0016] Furthermore, the protective layer is coated on the outside of the outer braided electrode to play the role of mechanical protection, waterproofing and anti-corrosion.
[0017] In the present invention, each energy storage unit is electrically insulated and physically isolated through an intermediate separator layer, and circuit connection is achieved through current collector material fibers to meet the working requirements of different energy storage units.
[0018] The composite fiber energy storage device of the present invention has a combination of multiple energy storage units of the same type or different types, and realizes series and / or parallel circuit connection through a multi-layer braided tube structure, and flexibly adjusts the output performance of the device, for example, it can improve the capacity, power or voltage of the device to meet complex application requirements.
[0019] The present invention aims at the problems of weak interlayer bonding, limited material selection, unstable structure, etc. existing in the winding and concentric extrusion preparation processes. By introducing a weaving process and utilizing the weavable characteristics of fiber materials, the functional fibers such as electrode material composite fibers, diaphragm material fibers, and current collector material fibers are woven layer by layer to form an integrated multi-layer fiber braided tube structure, which significantly enhances the mechanical bonding between the layers, improves the structural stability and safety of the energy storage unit and the composite fiber energy storage device, avoids interlayer separation and material shedding, and fundamentally solves the technical problems of weak interlayer bonding and poor structural stability of existing energy storage devices. The present invention introduces the weaving process into the preparation of energy storage units and composite fiber energy storage devices, broadens the application field of weaving technology, and also provides a new idea for the manufacture of energy storage devices.
[0020] The existing roll-to-roll process is complicated, requiring multiple coating, drying, winding and other steps, with low preparation efficiency, making it difficult to achieve large-scale production. The weaving process adopted by the present invention is continuous, controllable and efficient, which simplifies the preparation process, reduces multiple coating, drying and other steps, improves production efficiency, reduces manufacturing costs, and facilitates large-scale production. The present invention adopts a weaving process, the weaving speed is controllable, the production capacity is easy to enlarge, and it is helpful to achieve large-scale production; the weaving equipment is relatively simple, the environmental requirements are low, it is easy to operate and maintain, and the production cost is reduced.
[0021] The weaving process adopted in the present invention has good compatibility with the morphology and properties of fiber materials, strong adaptability, and is compatible with the fiber forms of a variety of active materials, conductive materials and functional materials, such as nanofibers, micron fibers and functionalized composite fibers, breaking through the limitations of material selection, providing a broad space for performance optimization, and improving the energy density, power density and cycle life of energy storage units and composite fiber energy storage devices.
[0022] The present invention uses a continuous, controllable and flexible weaving process to prepare energy storage units and composite fiber energy storage devices thereof. In the same production process, fiber materials with different functions can be woven and formed in a predetermined order and manner to achieve integrated assembly of functional layers, simplifying the preparation process and improving production efficiency. By adjusting the materials and weaving methods of each layer, the present invention can achieve the integration and combination of various energy storage units such as lithium-ion batteries, sodium-ion batteries, zinc-air batteries, and supercapacitors, meet the needs of different application scenarios, and enhance the functional diversity of composite fiber energy storage devices.
[0023] The present invention further prevents electrolyte leakage and electrode short circuit through a compact braided structure and an effective packaging method, thereby improving the safety and reliability of the device and meeting strict safety standards.
[0024] The present invention overcomes many technical bottlenecks in the structure, performance and preparation process of existing energy storage devices through innovative structural design (multi-layer fiber braided tube structure) and a preparation method using a braiding process, and provides a fiber energy storage device with high safety, high performance and easy large-scale production, which meets the urgent demand for energy storage devices in emerging application fields and promotes the development and application of energy storage technology. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 It is a structural schematic diagram of the energy storage unit in the present invention; Figure 2 It is a schematic diagram of the structure of the composite fiber energy storage device in the present invention; Figure 3 The present invention is a flow chart for preparing the composite fiber energy storage device. DETAILED DESCRIPTION
[0026] The present invention provides an energy storage unit (schematic diagram of the structure is shown in Figure 1 ), having a multi-layer fiber braided tube structure, the multi-layer fiber braided tube structure comprising an inner braided electrode, a middle diaphragm layer and an outer braided electrode; The composition of the inner braided electrode includes a first current collector-active electrode composite fiber and a first support material fiber; the chemical composition of the first current collector-active electrode composite fiber includes a first current collector fiber and a first electrode active material; the inner braided electrode is a positive electrode or an anode; The composition of the middle diaphragm layer includes diaphragm material; The outer braided electrode is composed of a second current collector-active electrode composite fiber and a second support material fiber; the chemical composition of the second current collector-active electrode composite fiber includes a second current collector fiber and a second electrode active material; The energy storage unit further comprises an electrolyte, and the electrolyte comprises solid electrolyte fibers or an electrolyte solution.
[0027] In the present invention, the arrangement and weaving density of the fibers in the energy storage unit can be adjusted according to the performance requirements of the device, so as to ensure the structural stability and performance consistency of each energy storage unit.
[0028] In the present invention, the total number of the first current collector-active electrode composite fibers and the first supporting material fibers in the inner woven electrode is preferably 2 to 24, and in specific embodiments may be 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23 or 24.
[0029] In the present invention, the root number ratio of the first current collector-active electrode composite fiber and the first support material fiber in the inner woven electrode is preferably 1-23:1, and in specific embodiments it can be 1:1, 2:1, 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1, 10:1, 11:1, 12:1, 13:1, 14:1, 15:1, 16:1, 17:1, 18:1, 19:1, 20:1, 21:1, 22:1 or 23:1.
[0030] In the present invention, the diameters of the first current collector fiber and the second current collector fiber are independently preferably 5-300 μm, and in specific embodiments may be 5 μm, 10 μm, 20 μm, 30 μm, 40 μm, 50 μm, 100 μm, 150 μm, 200 μm, 250 μm or 300 μm.
[0031] In the present invention, the diameters of the first electrode active material fibers and the second electrode active material fibers are independently preferably 100 nm to 300 μm, and in specific embodiments may be 100 nm, 200 nm, 300 nm, 500 nm, 1 μm, 5 μm, 10 μm, 20 μm, 25 μm, 50 μm, 100 μm, 150 μm, 200 μm, 250 μm or 300 μm.
[0032] In the present invention, the thickness of the inner braided electrode, the middle diaphragm layer and the outer braided electrode is preferably independently 1 to 1000 μm, and in specific embodiments may be 1 μm, 5 μm, 10 μm, 20 μm, 50 μm, 100 μm, 200 μm, 300 μm, 400 μm, 500 μm, 600 μm, 700 μm, 800 μm, 900 μm or 1000 μm. In the present invention, the inner braided electrode is used as a cathode or negative electrode, and the outer braided electrode is used as an anode or positive electrode.
[0033] In the present invention, the total number of the second current collector-active electrode composite fibers and the second supporting material fibers in the outer woven electrode is preferably 2 to 24, and in specific embodiments may be 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23 or 24.
[0034] In the present invention, the root number ratio of the second current collector-active electrode composite fibers to the second supporting material fibers in the outer woven electrode is preferably 1-23:1, and in specific embodiments it can be 1:1, 2:1, 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1, 10:1, 11:1, 12:1, 13:1, 14:1, 15:1, 16:1, 17:1, 18:1, 19:1, 20:1, 21:1, 22:1 or 23:1.
[0035] In the present invention, the first current collector fiber and the second current collector fiber independently preferably include at least one of metal fiber, carbon fiber containing metal coating and carbon fiber. In the present invention, the metal fiber preferably includes metal fiber preferably includes metal elemental fiber, metal fiber containing metal coating, alloy metal fiber or alloy fiber containing metal coating, more preferably includes copper fiber, aluminum fiber, titanium fiber, gold fiber, nickel fiber, copper-plated aluminum fiber, nickel-plated copper fiber, gold-plated stainless steel fiber or stainless steel fiber; the carbon fiber containing metal coating preferably includes gold-plated carbon fiber, silver-plated carbon fiber, copper-plated carbon fiber, platinum-plated carbon fiber or nickel-plated carbon fiber. In the present invention, the thickness of the metal coating in the metal fiber containing metal coating, the alloy fiber containing metal coating and the carbon fiber containing metal coating is independently preferably 2~3μm, and in a specific embodiment, it can be 2μm, 2.5μm or 3μm. In the present invention, the function of the first current collector fiber and the second current collector fiber is to realize circuit connection to meet the working requirements of different energy storage units.
[0036] The present invention does not specifically limit the preparation method of the first current collector fiber and the second current collector fiber, and a preparation method familiar to those skilled in the art may be used. The present invention uses fibers with good electrical conductivity and mechanical strength as current collection and transmission channels. In the present invention, the metal fiber is preferably pretreated before use, and the pretreatment preferably includes surface cleaning, removal of the oxide layer, and plasma surface activation treatment in sequence; the present invention performs the above-mentioned pretreatment on the metal fiber to help the metal fiber have good electrical conductivity and enhance the bonding force between the metal fiber and other fibers.
[0037] In the present invention, the content of electrolyte in the middle separator layer is preferably 20-80wt%, and in specific embodiments it can be 20wt%, 25wt%, 30wt%, 35wt%, 40wt%, 45wt%, 50wt%, 55wt%, 60wt%, 65wt%, 70wt%, 75wt% or 80wt%.
[0038] In the present invention, the diaphragm material preferably includes diaphragm material fibers or layered diaphragm materials, and the diaphragm material fibers preferably include at least one of Nafion fibers, polyethylene fibers, polyacrylonitrile fibers (PAN), polypropylene fibers (PP), polytetrafluoroethylene fibers, polyimide fibers, polyethersulfone fibers (PES), polyurethane fibers (PU) and polytetrafluoroethylene-hexafluoropropylene copolymer fibers (PVDF-HFP); the layered diaphragm material preferably includes a ceramic coated diaphragm, an alumina coated diaphragm or a silica coated diaphragm (SiO2); the ceramic coated diaphragm preferably includes an alumina coated diaphragm, a zirconium oxide coated diaphragm or a titanium oxide coated diaphragm; the alumina coated diaphragm preferably includes an alumina coated polypropylene diaphragm, an alumina coated polyethylene diaphragm or an alumina coated polyester diaphragm; the silica coated diaphragm preferably includes a silica coated polypropylene diaphragm, a silica coated polyethylene diaphragm or a silica coated nylon diaphragm. In the present invention, when the diaphragm material is diaphragm material fiber, the composition of the middle diaphragm layer also includes third support material fiber and / or solid electrolyte fiber.
[0039] In the present invention, the method for preparing the diaphragm material preferably comprises the following steps: dissolving the diaphragm material in a solvent, and preparing the diaphragm material by electrospinning, melt-blowing or blow molding. The present invention does not specifically limit the type of the solvent, as long as it can dissolve the diaphragm material. The present invention does not specifically limit the process conditions of the electrospinning, melt-blowing or blow molding, and the process conditions familiar to those skilled in the art can be used.
[0040] In the present invention, the middle diaphragm layer preferably has a porous fiber structure. The present invention uses a fiber material with good electrical insulation, ion conductivity and mechanical strength to prepare a porous fiber structure to form the middle diaphragm layer. In the present invention, the role of the middle diaphragm layer is to provide electrical isolation and physical isolation to prevent direct contact between electrodes, while allowing ions to pass through to ensure the normal progress of the electrochemical reaction.
[0041] In the present invention, the first supporting material fiber and the second supporting material fiber independently preferably include at least one of polytetrafluoroethylene fiber (PTFE), polyvinylidene fluoride (PVDF) fiber, polyethylene fiber (PE), polyimide fiber (PI), aramid fiber, glass fiber, carbon fiber, polyetheretherketone (PEEK) fiber, fluororubber fiber and nano-ceramic fiber; the polyethylene fiber preferably includes at least one of porous polyethylene fiber and high-strength polyethylene fiber; the high-strength polyethylene fiber preferably includes Spectra® fiber; the fluororubber fiber preferably includes one or more of fluorosilicone rubber fiber and perfluoroether rubber fiber; the nano-ceramic fiber preferably includes at least one of alumina ceramic fiber, aluminum silicate fiber, silicon carbide fiber and zirconium oxide fiber. In the present invention, the diameter of the first supporting material fiber is preferably 100nm~300μm, and in specific embodiments, it can be 100nm, 200nm, 300nm, 500nm, 1μm, 5μm, 10μm, 20μm, 25μm, 50μm, 100μm, 150μm, 200μm, 250μm or 300μm. The supporting material fiber used in the present invention has high strength, and the supporting material fiber is mixed and woven into each layer, which can provide axial and radial strength for the energy storage unit as a whole, and improve the mechanical strength and stability of the overall structure of the energy storage unit.
[0042] In the present invention, the energy storage unit further includes an electrolyte, and the electrolyte includes solid electrolyte fibers or an electrolyte solution; the solid electrolyte fibers are preferably distributed in the middle separator layer, and the electrolyte solution is distributed in the multi-layer fiber braided tube structure.
[0043] In the present invention, the energy storage unit preferably includes a metal ion battery, a metal-air battery, a flow battery, a supercapacitor, a dry cell, a fuel cell, an all-solid-state battery or a redox flow battery; the metal ion battery preferably includes a lithium ion battery, a sodium ion battery, a magnesium ion battery, an aluminum ion battery or a potassium ion battery.
[0044] In the present invention, the positive electrode active material of the lithium ion battery preferably includes at least one of lithium iron phosphate (LiFePO4), nickel cobalt manganese oxide ternary material (NCM), nickel cobalt aluminum oxide ternary material (NCA), lithium cobalt oxide (LiCoO2) and lithium manganese oxide (LiMn2O4). In the present invention, the negative electrode active material of the lithium ion battery preferably includes graphite, silicon carbon composite material (Si-C Composite), hard carbon (Hard Carbo), lithium titanate (Li4Ti5O 12 ) and at least one of reduced graphene oxide (rGO); the silicon-carbon composite material preferably comprises SiO x-C, silicon / graphene and silicon / carbon fiber. In the present invention, the electrolyte of the lithium ion battery preferably includes LiPF6 / EC / DMC electrolyte, LiFSI / EC / EMC electrolyte, LiPF6 / EC / DMC / DEC electrolyte or LiTFSI / ethanol / water electrolyte. Among them, EC is ethylene carbonate, DMC is dimethyl carbonate, EMC is methyl carbonate, and DEC is diethyl carbonate.
[0045] In the present invention, the positive electrode active material of the sodium ion battery preferably includes Prussian blue analogues, layered sodium manganese oxide (Na 0.44 MnO2), sodium vanadium oxide (Na X V2O5) and sodium titanate (Na2Ti3O7). In the present invention, the negative electrode active material of the sodium ion battery preferably includes at least one of hard carbon, metallic tin (Sn), tin-sodium alloy (Sn-Na Alloy), antimony-based alloy (Sb-based Alloy) and phosphorus-based compounds (Phosphorus-based Compounds); the Prussian blue compound preferably includes sodium ferrocyanide (Na x The antimony-based alloy preferably includes at least one of tin-antimony alloy and sodium-antimony alloy; the phosphorus-based compound preferably includes at least one of phosphorus-tin alloy, phosphorus-antimony alloy, phosphorus-sodium alloy, phosphorus-aluminum alloy, sodium-phosphorus oxide, phosphate and polyphosphate. In the present invention, the electrolyte of the sodium ion battery preferably includes NaClO4 / EC / PC electrolyte, NaPF6 / EC / DMC electrolyte, NaPF6 / EC / DMC / DEC electrolyte or NaTFSI / ethanol / water electrolyte; wherein PC is propylene carbonate.
[0046] In the present invention, the positive electrode active material of the magnesium ion battery preferably includes at least one of transition metal sulfides, transition metal oxides and sulfur (S); the transition metal sulfide preferably includes at least one of molybdenum disulfide, tungsten disulfide, vanadium sulfide and cobalt sulfide; the transition metal oxide preferably includes at least one of cobalt oxide, manganese oxide, iron oxide, copper oxide, titanium oxide, tungsten oxide and chromium oxide. In the present invention, the negative electrode active material of the magnesium ion battery preferably includes at least one of metal magnesium (Mg) and magnesium alloy (Magnesium Alloy); the magnesium alloy preferably includes at least one of magnesium aluminum alloy, magnesium aluminum zinc alloy, magnesium zinc titanium alloy and magnesium calcium alloy. In the present invention, the electrolyte of the magnesium ion battery preferably includes MgCl2 aqueous solution, MgCl2 / DME / DMM electrolyte, MgTFSI2 / DOL / EC electrolyte, MgFSI2 / DOL / DMC electrolyte, Mg(BH4)2 / THF / EC electrolyte; wherein DMM is dimethylformal, DOL is 1,2-dioxane, and THF is tetrahydrofuran.
[0047] In the present invention, the positive electrode active material of the aluminum ion battery preferably includes at least one of graphite and polyanionic compounds; the polyanionic compounds preferably include at least one of aluminum phosphate, trisodium aluminum phosphate, aluminum titanium carbide Ti2AlC, aluminum vanadate and aluminum fluoride. In the present invention, the negative electrode active material of the aluminum ion battery preferably includes at least one of metal aluminum, aluminum alloy and Al2O3 / graphite composite material; the aluminum alloy preferably includes Al-Cu alloy. In the present invention, the electrolyte of the aluminum ion battery preferably includes AlCl3 / NaCl / DMSO electrolyte, AlF3 / LiF / DMSO electrolyte, AlCl3 / DOL electrolyte, Al2(SO4)3 / water electrolyte or AlCl3 / benzene electrolyte; wherein DMSO is dimethyl sulfoxide.
[0048] In the present invention, the positive electrode active material of the potassium ion battery preferably includes a Prussian blue compound and a layered potassium manganese oxide (K X MnO2). In the present invention, the negative electrode active material of the potassium ion battery preferably includes at least one of graphite and hard carbon. In the present invention, the electrolyte of the potassium ion battery preferably includes KPF6 / EC / DMC electrolyte, KPF6 / DEC electrolyte, KPF6 / DMC electrolyte, KCl / DOL electrolyte, KPF6 / EMIM BF4 electrolyte or K2SO4 / water electrolyte.
[0049] In the present invention, the metal-air battery preferably includes a zinc-air battery, an aluminum-air battery, an iron-air battery, a sodium-air battery, a lithium-air battery or a magnesium-air battery.
[0050] In the present invention, the positive electrode catalytic material of the metal-air battery preferably includes at least one of manganese oxide, cobalt oxide, nickel oxide, graphite, activated carbon, carbon nanotubes (CNTs), organic metal framework, cobalt iron oxide, cobalt chromium oxide, platinum and gold. In the present invention, the negative electrode active material of the zinc-air battery preferably includes at least one of metal zinc (Zn), zinc alloy (ZincAlloy), zinc-titanium composite (Zn-Ti Composite) and zinc-carbon composite (Zn-C Composite). In the present invention, the electrolyte of the metal-air battery preferably includes KOH aqueous solution, NaOH aqueous solution, ZnCl2 aqueous solution, NaCl aqueous solution, NaOH ethanol solution or NaOH glycerol solution.
[0051] In the present invention, the positive electrode active material of the flow battery preferably includes at least one of vanadium oxide, iron oxide, lead oxide, zinc oxide and graphene. In the present invention, the negative electrode active material of the flow battery preferably includes at least one of porous activated carbon, carbon nanotubes, zinc, iron and lead. In the present invention, the electrolyte of the flow battery preferably includes at least one of VOSO4, ZnSO4, ZnCl2, FeSO4, FeCl2 and PbSO4; the flow battery preferably includes an all-vanadium flow battery, an iron-chromium flow battery, a zinc flow battery or a lead flow battery.
[0052] In the present invention, the electrode active material and the negative electrode active material of the supercapacitor independently preferably include at least one of activated carbon, carbon nanotubes, graphene, conductive polymers, reduced graphene oxide, carbon nanofibers (CNF) and carbon aerogel; the conductive polymer preferably includes at least one of polyaniline (PANI), poly(3,4-ethylenedioxythiophene) (PEDOT), polypyrrole (PPy), poly-p-phenylenediamine (PPD), polythiophene (PTh), poly(3,4-difluorothiophene) (P3DFT) and poly(thiophene-vinylbenzene) (PThVB).
[0053] In the present invention, the positive electrode active material of the dry cell preferably includes at least one of manganese dioxide-graphite composite material, nickel hydroxide and silver oxide. In the present invention, the negative electrode active material of the dry cell preferably includes at least one of zinc-carbon nanotube composite material, zinc, lithium, graphite and hydrogenated alloy; the hydrogenated alloy preferably includes at least one of nickel-hydrogen alloy, magnesium-hydrogen alloy, lithium-hydrogen alloy and sodium-hydrogen alloy. In the present invention, the electrolyte of the dry cell preferably includes a mixture of NH4Cl and ZnCl2, ZnSO4 or KOH; the mass ratio of NH4Cl and ZnCl2 in the mixture of NH4Cl and ZnCl2 is preferably 1-4:1, and in specific embodiments it can be 1:1, 1.5:1, 2:1, 2.5:1, 3:1, 3.5:1 or 4:1.
[0054] In the present invention, the cathode active material and the anode active material of the fuel cell independently preferably include at least one of platinum-based catalysts (Pt-based Catalysts), palladium-based catalysts (Pd-based Catalysts) and non-precious metal catalysts (Non-Precious Metal Catalysts); the non-precious metal catalyst preferably includes at least one of an iron-based catalyst, a cobalt-based catalyst, a nickel-based catalyst, a copper-based catalyst, a nitrogen-doped carbon-based catalyst, a metal nitride catalyst, a Co-Fe alloy and a Co-Ni alloy; the platinum-based catalyst preferably includes a Pt / C catalyst, and the Pt content in the Pt / C catalyst is preferably 20-50wt%, and in a specific embodiment it can be 20wt%, 25wt%, 30wt%, 35wt%, 40wt%, 45wt% or 50wt%; the palladium-based catalyst preferably includes at least one of Pd / C, PdCu alloy, PdNi alloy and PdCuNi alloy; The iron-based catalyst preferably includes at least one of Fe-NC catalyst, ferrosoferric oxide and Fe / C; the cobalt-based catalyst preferably includes at least one of Co / C, cobalt oxide (Co3O4) and Co-NC catalyst; the nickel-based catalyst preferably includes at least one of Ni / C, Ni3Fe alloy and nickel oxide (NiO); the copper-based catalyst preferably includes at least one of Cu / C catalyst and copper oxide; the nitrogen-doped carbon-based catalyst preferably includes at least one of nitrogen-doped activated carbon, nitrogen-doped multi-walled carbon nanotubes, nitrogen-doped graphene and nitrogen-doped graphene oxide; the metal nitride catalyst preferably includes at least one of iron nitride, cobalt nitride, nickel nitride, titanium nitride and molybdenum nitride. In the present invention, the electrolyte of the fuel cell preferably includes Li2SO4 / SiO2 nanocomposite electrolyte, liquid phosphoric acid, KOH aqueous solution or K2CO3 aqueous solution.
[0055] In the present invention, the positive electrode active material of the all-solid-state battery preferably includes at least one of lithium cobalt oxide, lithium iron phosphate, lithium nickel oxide, nickel cobalt manganese oxide, nickel cobalt oxide, lithium manganese oxide, lithium titanate, lithium sulfide, lithium silicate, sulfur-lithium composite material and lead titanate. In the present invention, the negative electrode active material of the all-solid-state battery preferably includes at least one of lithium, lithium alloy, graphite, silicon and sodium. In the present invention, the solid electrolyte of the all-solid-state battery preferably includes at least one of lithium salt polymer solid electrolyte, perovskite oxide electrolyte, NASICON, LISICON and sulfide solid electrolyte; the sulfide solid electrolyte preferably includes Li 10 GeP2S 12 (LGPS).
[0056] In the present invention, the multi-layer fiber braided tube structure is preferably a concentric or eccentric multi-layer fiber braided tube structure.
[0057] In the present invention, the energy storage unit preferably further includes a protective layer located on the surface of the outer braided electrode. In the present invention, the thickness of the protective layer is preferably 30-500 μm, and in a specific embodiment, it can be 30 μm, 40 μm, 50 μm, 60 μm, 70 μm, 80 μm, 90 μm, 100 μm, 200 μm, 300 μm, 400 μm or 500 μm. In the present invention, the composition of the protective layer preferably includes polymer fibers, and more preferably includes at least one of polyimide (PI) fibers, polytetrafluoroethylene (PTFE) fibers and aramid fibers. In the present invention, the diameter of the polymer fiber is preferably 15-300 μm, and in a specific embodiment, it can be 15 μm, 20 μm, 30 μm, 40 μm, 50 μm, 60 μm, 70 μm, 80 μm, 90 μm, 100 μm, 150 μm, 200 μm, 250 μm or 300 μm. In the present invention, the protective layer is used to provide mechanical protection and waterproof and anti-corrosion functions.
[0058] In the present invention, the energy storage unit preferably further includes an encapsulation layer located on the surface of the outer braided electrode or the protective layer. In the present invention, the encapsulation material of the encapsulation layer preferably includes a polytetrafluoroethylene heat shrink tube, a polyvinylidene fluoride film, an epoxy resin or a silicone rubber. In the present invention, the thickness of the encapsulation layer is preferably 0.1 to 5 mm, and in a specific embodiment it can be 0.1 mm, 0.5 mm, 1 mm, 2 mm, 3 mm, 4 mm or 5 mm. In the present invention, the encapsulation layer plays the role of waterproofing, anti-corrosion and mechanical protection.
[0059] The present invention also provides a method for preparing the energy storage unit described in the above technical solution, comprising the following steps: Performing a first weaving on the raw materials for preparing the inner layer braided electrode to obtain the inner layer braided electrode; The raw materials for preparing the middle diaphragm layer are subjected to a second weaving or winding process on the surface of the inner woven electrode to obtain the middle diaphragm layer; The raw materials for preparing the outer braided electrode are subjected to a third weaving process on the surface of the middle diaphragm layer to form an outer braided electrode, thereby obtaining the energy storage unit; When the electrolyte is a solid electrolyte, solid electrolyte fibers are added during the second weaving or winding process; When the electrolyte is an electrolyte solution, the method further includes: placing the multi-layer fiber braided tube obtained by the third weaving in the electrolyte solution for immersion or electrophoretic deposition; or spraying the multi-layer fiber braided tube obtained by the third weaving with the electrolyte solution.
[0060] Unless otherwise specified, the materials and equipment used in the present invention are all commercially available products in the art.
[0061] The present invention performs a first weaving on the raw materials for preparing the inner layer braided electrode to obtain the inner layer braided electrode.
[0062] In the present invention, the first weaving preferably includes at least one of circular weaving, flat weaving, three-dimensional weaving, warp knitting, weft knitting, biaxial weaving, multiaxial weaving, spiral weaving, knitting, shuttleless weaving, seamless weaving, weft knitting and warp knitting. The present invention has no special restrictions on the process conditions of the first weaving, which can be determined according to the material properties and performance requirements of different energy storage units.
[0063] In the present invention, the raw materials for preparing the inner braided electrode include first current collector-active electrode composite fibers and first support material fibers; the first electrode active material includes first electrode active material fibers or first electrode active material particles.
[0064] In the present invention, when the first electrode active material can independently form fibers, the first weaving is preferably: twisting or core-spinning the first electrode active material fibers and the first current collector fibers to obtain first current collector-active electrode composite fibers.
[0065] In the present invention, the method for preparing the first electrode active material fiber preferably comprises the following steps: mixing the first electrode active material, a conductive additive, a binder and a solvent, and spinning to obtain the first electrode active material fiber. In the present invention, the spinning preferably comprises electrospinning, melt spinning, solution spinning or gel spinning. The present invention has no special restrictions on the types of the conductive additive, binder and solvent and the spinning conditions, as long as the first electrode active material fiber can be obtained.
[0066] In the present invention, when the first electrode active material cannot form fibers independently, the method for preparing the first current collector-active electrode composite fiber preferably includes the following steps: compounding the first current collector fiber with the first electrode active material particles to obtain the first current collector-active electrode composite fiber. In the present invention, the compounding preferably includes coating, chemical deposition or pore structure infiltration; the present invention has no special restrictions on the conditions of the coating, chemical deposition or pore structure infiltration, as long as the first electrode active particles can be uniformly loaded on the first current collector fiber.
[0067] After the inner braided electrode is obtained, the present invention performs a second weaving or winding of the raw materials for preparing the middle diaphragm layer on the surface of the inner braided electrode to obtain the middle diaphragm layer.
[0068] In the present invention, the raw materials for preparing the middle diaphragm layer include diaphragm material, and preferably also include supporting material fibers.
[0069] In the present invention, the method and process conditions of the second weaving are the same as those of the first weaving, and will not be described in detail here. The present invention has no special restrictions on the conditions of the second weaving or winding, as long as the raw materials for preparing the middle diaphragm layer are tightly coated on the outer surface of the inner woven electrode to form the middle diaphragm layer.
[0070] After obtaining the middle diaphragm layer, the present invention performs a third weaving process on the surface of the middle diaphragm layer to form an outer layer of braided electrodes using raw materials for preparing the outer layer of braided electrodes, thereby obtaining the energy storage unit.
[0071] In the present invention, the raw materials for preparing the outer braided electrode include second current collector-active electrode composite fibers and second support material fibers; the chemical composition of the second current collector-active electrode composite fibers includes second current collector fibers and second electrode active materials.
[0072] In the present invention, the preparation methods of the second current collector-active electrode composite fiber and the outer woven electrode are respectively the same as those of the first current collector-active electrode composite fiber and the first woven electrode, and are not described in detail herein.
[0073] In the present invention, the electrolyte is introduced by preferably including electrolyte fiber weaving, impregnation, spraying or electrophoretic deposition; the impregnation preferably includes vacuum impregnation or pressure impregnation. The present invention adopts the above-mentioned method to introduce the electrolyte, which helps to evenly distribute and fully infiltrate the electrolyte in the energy storage unit.
[0074] In the present invention, when the electrolyte is a solid electrolyte, solid electrolyte fibers are added during the second weaving or winding process, that is, the electrolyte is introduced by using electrolyte fiber weaving.
[0075] In the present invention, when the electrolyte is an electrolyte solution, it also includes: placing the multi-layer fiber braided tube obtained by the third weaving in the electrolyte solution for immersion or electrophoretic deposition; or spraying the multi-layer fiber braided tube obtained by the third weaving with the electrolyte solution. The present invention has no special restrictions on the time, temperature, pressure, electrophoretic voltage and current density of the immersion, which can be adjusted according to the fiber porosity, energy storage unit size and electrolyte properties to enable the electrolyte to be fully infiltrated and evenly distributed.
[0076] After completing the third weaving and introducing the electrolyte, the present invention preferably further comprises: weaving a protective layer on the outer surface of the outer weaving electrode using the raw materials for preparing the protective layer.
[0077] The present invention preferably further comprises: using packaging materials to perform overall packaging to obtain an energy storage unit. The present invention has no special limitation on the overall packaging, and packaging operations and packaging conditions well known to those skilled in the art can be used.
[0078] The present invention also provides a composite fiber energy storage device (schematic diagram of the structure is shown in Figure 2 ), having an overall multi-layer braided tube structure consisting of n layers of energy storage units, and a protective layer is arranged between adjacent energy storage units; n is an integer not less than 2; the types of the n layers of energy storage units are the same or different; the n layers of energy storage units are connected in series and / or in parallel; the energy storage unit is the energy storage unit described in the above technical solution or the energy storage unit prepared by the preparation method described in the above technical solution.
[0079] In the present invention, when n energy storage units are of the same type, the composite fiber energy storage device has a single type of energy storage mode. At this time, multiple energy storage units of the same type are integrated in the composite fiber energy storage device, and series and / or parallel circuit connections are achieved through a multi-layer braided tube structure, which can significantly improve the capacity, power or voltage of the composite fiber energy storage device to meet the requirements of different voltages and capacities.
[0080] In the present invention, when n energy storage units are different types of energy storage units, two or more different types of energy storage units are integrated in the composite fiber energy storage device, such as lithium-ion batteries and supercapacitors, sodium-ion batteries and zinc-air batteries, magnesium-ion batteries and fuel cells, etc., and the integration of different types of energy storage methods is achieved through a multi-layer braided tube structure.
[0081] In the present invention, the series connection is preferably a second current collector fiber in the upper layer of energy storage unit and a first current collector fiber in the lower layer of energy storage unit in series; the series connection is a circuit connection; the circuit connection preferably includes a series connection through a conductive fiber, a welding lead or a conductive connector. The present invention adopts a series connection to achieve voltage superposition. The present invention combines multiple energy storage units of the same type, which means that multiple energy storage units of the same type are integrated in the device, and a series and / or parallel circuit connection is achieved through a multi-layer braided tube structure to increase the capacity, power or voltage of the device.
[0082] In the present invention, each energy storage unit is electrically insulated and physically isolated through an intermediate separator layer, and circuit connection is achieved through current collector material fibers to meet the working requirements of different energy storage units.
[0083] In the present invention, the parallel connection is preferably that the first current collector fiber of the energy storage unit is connected in parallel with the first current collector fiber, and the second current collector fiber is connected in parallel with the second current collector fiber; the parallel connection method is preferably circuit connection; the circuit connection preferably includes parallel connection through conductive fibers, welding leads or conductive connectors. The positive electrodes and the negative electrodes of the same energy storage unit are connected in parallel through conductive fibers or wire materials, which can improve the current output capacity.
[0084] In the present invention, the dynamic switching of different energy storage modes of the composite fiber energy storage device is preferably adjusted by a circuit connection mode; the circuit connection mode preferably includes at least one of a switching switch, a dynamic electrode connector and an electronic control unit; the different energy storage modes preferably include at least one of a high voltage mode, a high power mode and a long endurance mode.
[0085] In the present invention, the composite fiber energy storage device preferably includes a lithium ion battery unit, a sodium ion battery unit, a zinc air battery unit and a supercapacitor unit in sequence from the inside to the outside, and each energy storage unit is connected in series and / or in parallel.
[0086] In the present invention, the composite fiber energy storage device preferably includes lithium ion battery cells, sodium ion battery cells, supercapacitor cells and zinc air battery cells in sequence from the inside to the outside, and each energy storage unit is connected in series and / or in parallel to meet the requirements of different voltages and capacities.
[0087] In the present invention, there is no special limitation on the thickness, length and shape of the composite fiber energy storage device, which can be customized according to actual application requirements, such as linear, strip, tubular or fabric-shaped, to adapt to applications in different fields such as wearable devices, smart textiles, flexible electronics, etc.
[0088] The multi-unit combination of a single type of energy storage unit and the composite combination of different types of energy storage units in the composite fiber energy storage device provided by the present invention are both realized through a multi-layer braided tube structure, and a layered composite of multiple energy storage units is formed by expanding the energy storage unit.
[0089] In the present invention, the composite fiber energy storage device preferably further comprises an encapsulation layer located on the surface of the integral multilayer braided tube structure. In the present invention, the encapsulation material of the encapsulation layer preferably comprises a polytetrafluoroethylene heat shrink tube, a polyvinylidene fluoride film, an epoxy resin or a silicone rubber. In the present invention, the thickness of the encapsulation layer is preferably 0.1 to 5 mm, and in a specific embodiment it can be 0.1 mm, 0.5 mm, 1 mm, 2 mm, 3 mm, 4 mm or 5 mm. In the present invention, the encapsulation layer plays the role of waterproofing, anti-corrosion and mechanical protection.
[0090] The present invention also provides a method for preparing the composite fiber energy storage device described in the above technical solution, comprising the following steps: (1) performing a first weaving on the raw materials for preparing the inner layer braided electrode to obtain the inner layer braided electrode; The raw materials for preparing the middle diaphragm layer are subjected to a second weaving or winding process on the surface of the inner woven electrode to obtain the middle diaphragm layer; The raw materials for preparing the outer braided electrode are braided for the third time on the surface of the middle diaphragm layer to form the outer braided electrode to obtain the first layer of energy storage units, and a protective layer is prepared on the surface of the first layer of energy storage units; When the electrolyte is a solid electrolyte, solid electrolyte fibers are added during the second weaving or winding process; When the electrolyte is an electrolyte solution, the method further comprises: placing the multi-layer fiber braided tube obtained by the third weaving in the electrolyte solution for immersion or electrophoretic deposition; or spraying the multi-layer fiber braided tube obtained by the third weaving with the electrolyte solution; (2) Repeat step (1) n-1 times on the surface of the protective layer to obtain the composite fiber energy storage device.
[0091] In the present invention, the preparation method of the first layer energy storage unit is preferably the same as the preparation method of the energy storage unit described in the above technical solution, and will not be repeated here.
[0092] The present invention preferably also includes the step of repeating step (1) n-1 times on the surface of the protective layer to obtain an overall multilayer braided tube structure, and sequentially performing electrode lead-out, connection point sealing and overall packaging to obtain a composite fiber energy storage device. Specifically, the collector fiber end of each energy storage unit is connected to the electrode circuit, the connection point is sealed, and then the overall packaging is performed using a packaging material. The above-mentioned treatment of the present invention helps to avoid electrolyte leakage and improve the safety and reliability of the composite fiber energy storage device. In the present invention, the connection point sealing is preferably performed by sealing with a sealant, epoxy resin, heat shrink tubing or silicone rubber. In the present invention, the electrode lead-out, connection point sealing and packaging are preferably performed under a protective atmosphere, and the protective atmosphere preferably includes nitrogen, argon or helium.
[0093] The present invention also provides the use of the energy storage unit described in the above technical solution, the energy storage unit obtained by the preparation method described in the above technical solution, the composite fiber energy storage device described in the above technical solution, or the composite fiber energy storage device obtained by the preparation method described in the above technical solution in wearable devices, smart textiles or flexible electronics. The energy storage unit and composite fiber energy storage device provided by the present invention solve the safety problems of current roll-to-roll capacitors or batteries and existing fiber energy storage devices in the form of winding and concentric extrusion, and improve the simplicity and efficiency of preparation. The energy storage unit and composite fiber energy storage device provided by the present invention have the characteristics of high safety, flexibility, light weight, high energy density and high power density, and are suitable for wearable devices, smart textiles, portable electronic products, flexible electronics and other fields, meeting the demand for high-performance, safe and reliable, and easy-to-produce energy storage devices.
[0094] The present invention overcomes many technical bottlenecks in the structure, performance and preparation process of existing energy storage devices through innovative structural design and preparation methods, and provides a high-safety, high-performance, and easy-to-scale production energy storage unit and composite fiber energy storage device, which meets the urgent needs of emerging application fields for energy storage devices and promotes the development and application of energy storage technology.
[0095] In order to further illustrate the present invention, the energy storage unit, composite fiber energy storage device, preparation method and application thereof provided by the present invention are described in detail below in combination with embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0096] Example 1: Fiber fuel cell based on proton exchange membrane fuel cell (PEMFC) 1. Material Preparation 1.1 Anode active material fiber (anode catalyst layer): Active material: 20wt% Pt / C catalyst, used to increase the rate of proton exchange reaction.
[0097] Preparation method: Pt / C catalyst, polytetrafluoroethylene (PTFE) aqueous dispersion and polyethylene oxide (PEO) were mixed and stirred to a uniform slurry, and the slurry was loaded into an electrospinning machine, the voltage was set to 15kV, the collection distance was set to 15cm, the spinning rate was 0.5mL / h, and the anode active material fiber with a diameter of 200nm was spun under vacuum, and dried in a drying oven at 100℃ for 8h. The concentration of Pt / C catalyst in the slurry was 10wt%, the concentration of PTFE was 40wt%, and the concentration of PEO was 1.5wt%.
[0098] 1.2. Anode current collector fiber: Material: Platinum-coated carbon fiber, 20 μm in diameter, with excellent electrical conductivity and catalytic activity.
[0099] Preparation method: Place the carbon fiber as the cathode in a platinum plating solution (composition of the platinum plating solution: H2PtCl6 concentration 15g / L, NaCl concentration 10g / L, solvent is water, and the platinum electrode is used as the electroplating anode), stir the reaction at 70°C for 6h, then wash with deionized water to neutrality, and dry to obtain the anode current collector fiber.
[0100] 1.3 Anode current collector-active electrode composite fiber: A double twister was used to twist and plied one of the above-mentioned anode active material fibers and one of the anode current collector fibers to form an anode current collector-active electrode composite fiber, with a twist of 500 twists / m.
[0101] 1.4. Cathode active material fiber (cathode catalyst layer): Active material: 20wt% Pt / C catalyst. The preparation method of cathode active material fiber is the same as that of anode active material fiber.
[0102] 1.5. Cathode current collector fiber: Material: Gold-coated carbon fiber, 20 μm in diameter.
[0103] Preparation method: In an electroplating tank, the carbon fiber is used as a cathode and immersed in a gold plating solution (HAuCl4 concentration 15g / L, H2SO4 concentration 75g / L, and a gold electrode is used as an electroplating anode). The electroplating reaction is carried out at room temperature for 3 hours until a uniform gold layer is formed on the surface to obtain a cathode current collector fiber.
[0104] 1.6 Cathode current collector-active electrode composite fiber: A cathode active material fiber and a cathode current collector fiber are twisted and plied using a two-for-one twister to form a cathode current collector-active electrode composite fiber, with a twist of 500 twists / m.
[0105] 1.7. Diaphragm material fiber (proton exchange membrane): Material: Nafion fiber.
[0106] Preparation method: Nafion solution (5wt% Nafion117) was electrospun under a high voltage electric field (voltage of 20 kV, collection distance of 15 cm, flow rate of 0.8 mL / h) to form Nafion fibers with a diameter of about 100 nm.
[0107] 1.8. Solid electrolyte material fiber: Material: Li2SO4 / SiO2 nanocomposite fiber.
[0108] Preparation method: Li2SO4 and SiO2 are dispersed in a mixed solution of polyethylene glycol (PEG) and water, stirred until uniform, and the resulting mixed solution (Li2SO4 concentration is 5wt%, SiO2 concentration is 5wt%, PEG concentration is 10wt%) is spun into solid electrolyte material fibers with a diameter of about 200nm by electrospinning technology at 20kV.
[0109] 1.9 Support material fiber: Material: PTFE fiber, diameter 25 μm.
[0110] 2. Device Preparation and Assembly 2.1 Preparation of inner braided anode (anode catalyst layer): Braided material configuration: 5 anode current collector-active electrode composite fibers mixed with 3 support material fibers.
[0111] Weaving process: Use 8 weaving machines to evenly distribute 5 anode current collector-active electrode composite fibers and 3 support material fibers on the weaving shuttle; set the weaving speed to 30r / min, maintain a constant weaving tension of 0.5N to prevent fiber material accumulation or entanglement; continuously observe the fiber arrangement during the weaving process to avoid uneven fiber accumulation leading to uneven catalyst distribution. After weaving, the inner braided tube is dried in a vacuum environment at 80℃ for 4h to remove the residual solvent in the spinning process and obtain the inner braided anode.
[0112] 2.2 Preparation of the middle membrane layer (proton exchange membrane layer): Braiding material configuration: 6 Nafion fibers and 2 Li2SO4 / SiO2 nanocomposite fibers are mixed in proportion.
[0113] Weaving process: Use 8 circular weaving machines to evenly distribute 6 Nafion fibers and 2 solid electrolyte fibers on the weaving shuttle; set the weaving speed to 20r / min, and evenly coat the surface of the inner braided electrode; keep the fiber tension uniform to avoid inconsistent proton exchange layer thickness due to uneven tension during weaving. After weaving, the obtained intermediate braided tube is heat treated in an environment of 80℃ with a humidity of 50% for 6 hours to ensure that the Nafion fiber and the solid electrolyte fiber form a stable proton exchange layer to obtain the intermediate separator layer.
[0114] 2.3 Preparation of outer braided cathode (cathode catalyst layer): Weaving material configuration: 5 cathode current collector-active electrode composite fibers and 3 support material fibers are mixed in proportion.
[0115] Weaving process: Use 8 circular weaving machines to evenly distribute 5 cathode current collector-active electrode composite fibers and 3 supporting material fibers; set the weaving speed to 20r / min to ensure that the fibers are neatly arranged and the middle separator layer is covered layer by layer; during the weaving process, check the bonding between the fiber layer and the middle layer regularly to ensure that the fiber layers are tightly bonded to prevent interlayer shedding. After weaving, the outer braided tube is dried in a vacuum environment at 70°C to remove the residual moisture and organic solvents during the weaving process to obtain the outer braided cathode.
[0116] 2.4 Protective layer weaving: If the application environment has high requirements for the weather resistance and mechanical strength of the device, a protective layer can be coated on the outer braided tube. Use high molecular weight polyimide (PI) fibers to weave 8 circles and evenly coat them on the surface of the outer braided cathode to form a protective layer, and obtain a multi-layer fiber braided tube structure energy storage device.
[0117] 2.5 Overall device packaging and electrode extraction: The woven multi-layer fiber braided tube structure energy storage device is cut to the required length (usually 10 cm), and the anode current collector fiber and the cathode current collector fiber are connected to the copper foil lead respectively using conductive glue. In an inert gas environment (such as argon), both ends of the fiber are encapsulated with epoxy resin to ensure that the electrode contact part is sealed without leakage, and fuel inlets are reserved at the positive and negative electrodes respectively. The outside of the device is wrapped and sealed with a polytetrafluoroethylene (PTFE) heat shrink tube to form an overall protection, and a fiber fuel cell based on a proton exchange membrane fuel cell is obtained.
[0118] 3. Performance testing and characterization of fiber fuel cells based on proton exchange membrane fuel cells Specific power test: At a current density of 50mA / cm², the specific power density of the device was tested and the result was 200mW / cm².
[0119] Bending test: Under the condition of bending radius of 5mm, 1000 bending cycles were repeated, and there was no obvious decline in device performance.
[0120] Corrosion resistance test: After immersion in an acidic environment (sulfuric acid adjusted to pH = 2) for 48 hours, cyclic voltammetry was used with a scanning voltage of 1.0V and a scanning rate of 25mV / S. The starting potential and catalytic activity of the catalytic reaction were evaluated by CV curves. The device catalytic performance retention rate of the test device exceeded 95%.
[0121] Example 2: Fiber energy storage device based on vanadium oxide flow battery 1. Material Preparation 1.1 Positive electrode active material fiber (vanadium oxide composite material layer): Active material: Vanadium oxide (VO2) and graphene composite.
[0122] Preparation method: VO2 and graphene nanosheets are mixed in a mass ratio of 70:30, dispersed in a mixed solvent of deionized water and ethanol (the volume ratio of deionized water and ethanol is 1:0.5), polyethylene glycol (PEG, the PEG concentration in the mixed slurry is 2wt%) is added as a fiber-forming agent, and stirred until uniform to obtain a mixed slurry, which is loaded into an electrospinning machine, the voltage is set to 18kV, the collection distance is set to 20cm, the spinning rate is 0.5mL / h, and the positive electrode fiber with a diameter of about 300nm is spun under a vacuum environment, and dried in an oven at 100℃ for 8h. Among them, the concentration of VO2 in the mixed slurry is 7wt%, and the volume ratio of deionized water and ethanol is 1:0.5.
[0123] 1.2 Negative electrode active material fiber (porous carbon composite material layer): Active materials: porous activated carbon and carbon nanotubes (CNTs) composite materials.
[0124] Preparation method: Activated carbon and carbon nanotubes are mixed in a mass ratio of 80:20, polyvinylidene fluoride (PVDF) is added as a binder, dispersed in N-methylpyrrolidone (NMP), stirred until uniformly dispersed, and the resulting dispersion is electrospun using electrostatic spinning technology, with the voltage set to 20kV, the collection distance set to 18cm, and the spinning rate set to 0.8mL / h, to form negative electrode active material fibers with a diameter of about 500nm. Among them, the concentration of activated carbon in the dispersion is 1.6wt%, and the concentration of PVDF is 5wt%.
[0125] 1.3 Diaphragm material fiber (porous polyethylene fiber): Material: porous polyethylene (PE) fiber.
[0126] Preparation method: Polyethylene was dissolved in a mixed solvent of dichloromethane and ethanol to form a 5wt% polyethylene solution (the volume ratio of dichloromethane to ethanol was 7:3). Electrospinning technology was used at a voltage of 15kV, a collection distance of 20cm, and a spinning rate of 0.8mL / h to prepare porous polyethylene fibers with a diameter of about 200nm.
[0127] 1.4 Electrolyte material fiber: Material: Sulfate electrolyte storage fiber (PAN fiber impregnated with VOSO4 solution).
[0128] Preparation method: VOSO4 solution (1M concentration, solvent is deionized water) is mixed and impregnated with polyacrylonitrile (PAN) fiber, and then the impregnated fiber is placed in a vacuum environment at 60°C and dried for 6 hours to ensure that the electrolyte is fully filled into the fiber pores to obtain sulfate electrolyte storage fiber.
[0129] 1.5 Positive and negative electrode current collector fibers: Material: Nickel fiber, diameter about 20μm.
[0130] Preparation method: A nickel wire with a diameter of 20 μm was immersed in a 10 wt % hydrochloric acid solution for deoxidation treatment for 5 min, rinsed with a large amount of deionized water and dried.
[0131] 1.6 Support Fiber: Materials: Aramid fibers, approximately 50 μm in diameter, are used to increase the mechanical strength and stability of the device.
[0132] Preparation method: Use a low-temperature plasma treatment machine to treat the surface of the aramid fiber with nitrogen plasma to enhance the bonding force with other fibers. The nitrogen flow rate is 30 sccm, the power is 100 W, and the treatment time is 5 min.
[0133] 1.7 Positive and negative current collectors-active electrode composite fibers: A positive electrode and a negative electrode active material fiber were twisted and plied with the above current collector fiber using a two-for-one twister to prepare a positive electrode and a negative electrode current collector-active electrode composite fiber, respectively, with a twist of 500 twists / m.
[0134] 2. Preparation and assembly of fiber energy storage devices based on vanadium oxide flow batteries 2.1 Preparation of inner braided electrode: Weaving material configuration: The positive electrode current collector-active electrode composite fibers and the supporting material fibers are mixed and woven in a ratio of 6:2.
[0135] Weaving process: Use 8 weaving machines to evenly place 6 positive electrode fluid-active electrode composite fibers and 2 supporting material fibers on the weaving shuttle; set the weaving speed to 25r / min, and adjust the tension of the fibers during weaving to a constant 0.5N to avoid the fibers from being too tight or too loose; during the weaving process, check the distribution of the fibers regularly to ensure uniform coverage of the electrode material on the current collector. After weaving, the inner braided tube is dried in a vacuum environment at 80°C for 6 hours to remove the residual solvent during the spinning process to obtain the inner braided positive electrode.
[0136] 2.2 Preparation of the middle diaphragm layer (diaphragm and electrolyte storage layer): Weaving material configuration: porous polyethylene diaphragm material fibers and VOSO4 electrolyte storage fibers are mixed and woven in a root ratio of 1:1.
[0137] Weaving process: Use 8 circular weaving machines to evenly distribute 4 porous polyethylene fibers and 4 electrolyte storage fibers on the weaving shuttle; set the weaving speed to 30r / min, and evenly weave along the surface of the inner braided positive electrode to form a middle diaphragm layer; keep the weaving tension uniform at about 0.5N to prevent the fibers from being too loose to increase porosity or too tight to cause electrolyte leakage. After weaving, place the resulting middle braided tube in a humidity-controlled environment at 50°C for 4 hours to ensure the bonding strength of the diaphragm and electrolyte fiber layers.
[0138] 2.3 Preparation of outer braided negative electrode Weaving material configuration: The negative electrode current collector-active electrode composite fibers and the supporting material fibers are mixed and woven in a ratio of 6:2.
[0139] Weaving process: Use 8 circular weaving machines to evenly distribute 6 negative current collector-active electrode composite fibers and 2 supporting material fibers on the weaving shuttle; use the middle separator layer as the core material and weave the outer layer at a speed of 25r / min to ensure that each layer of weaving fibers is tightly combined with the inner layer fibers to form a uniform and dense outer layer braided tube; check the bonding of the electrode fibers regularly during the weaving process to ensure that there is no fiber breakage or cross-stackage during the weaving process. After weaving, the outer layer braided tube is dried in a vacuum environment at 80℃ for 8h to remove all moisture and organic solvents to obtain the outer layer braided negative electrode.
[0140] 2.4 Protective layer weaving: In order to improve the mechanical strength of the device, an aramid fiber protective layer is added to the outer layer of the outer negative electrode braided tube. Using a 16-thread circular braiding machine, 16 50 μm aramid fibers are evenly woven on the outer layer of the negative electrode at a speed of 25 r / min and a constant tension of about 1 N to form a protective layer.
[0141] 2.5 Overall device packaging and electrode extraction: The woven multi-layer fiber braided tube structure flow battery is cut to the required length (15cm), and the positive and negative current collector fibers are connected to the copper foil leads respectively using conductive silver glue. In an inert gas environment (such as argon), epoxy resin is encapsulated at both ends of the fiber to ensure that there is no leakage in the electrolyte storage layer and no corrosion in the electrode contact part. A polytetrafluoroethylene heat shrink tube is used to cover the outer surface of the fiber device to form a waterproof sealing layer, thereby obtaining a fiber energy storage device based on a vanadium oxide flow battery.
[0142] 3. Performance testing and characterization of fiber energy storage devices based on vanadium oxide flow batteries Specific power test: At a current density of 50mA / cm², the specific power density of the device was tested and the result was 150mW / cm².
[0143] Bending test: Under the condition of bending radius of 10mm, 2000 bending cycles were repeated, and there was no obvious decline in device performance.
[0144] Electrochemical stability test: After soaking in an acidic environment (sulfuric acid adjusted to pH = 1.5) for 24 hours, the surface was cleaned with deionized water, and the battery was tested by cyclic voltammetry using an electrochemical workstation. The IV curve of the battery was recorded, and the redox peak area was calculated to represent the battery capacity. The area ratio of the redox peak before and after acid treatment, that is, the electrochemical performance retention rate, exceeded 92%.
[0145] Example 3: Fiber energy storage device based on sodium ion battery 1. Material Preparation 1.1 Positive electrode active material fiber Active material: layered sodium manganese oxide (Na 0.44 MnO2) nanoparticles.
[0146] Conductive additive: Carbon nanotubes (CNTs).
[0147] Binder: polyvinylidene fluoride (PVDF).
[0148] Preparation method: Na 0.44 MnO2, CNT and PVDF were mixed in a mass ratio of 80:10:10, N-methylpyrrolidone (NMP) solvent was added, and stirred for 4 h to form a uniform slurry (Na 0.44 The concentration of MnO2 was 16wt%). Electrospinning technology was used to prepare positive electrode active material fibers with a diameter of about 300nm. The spinning voltage was set to 18kV, the spinning rate was 0.6mL / h, and the collection distance was 15cm. After spinning, the fibers were dried in a vacuum drying oven at 80℃ for 12h to remove residual solvent.
[0149] 1.2 Negative electrode active material fiber Active materials: Hard Carbon and conductive carbon black fiber.
[0150] Binder: Sodium carboxymethyl cellulose (CMC).
[0151] Preparation method: Mix hard carbon, conductive carbon black and CMC in a mass ratio of 80:10:10, add a small amount of water to form a uniform slurry (the concentration of hard carbon is 8wt%). Load the slurry into an electrospinning machine, set the spinning voltage to 15kV, the spinning rate to 0.4mL / h, and the collection distance to 20cm to prepare negative electrode active material fibers with a diameter of about 200nm. After spinning, the fibers were dried at 70℃ for 8h.
[0152] 1.3 Fluid Collector Fiber Positive electrode current collector fiber: nickel-plated carbon fiber with a diameter of 20μm and a nickel layer thickness of 2~3μm.
[0153] Negative electrode current collector fiber: copper-coated aluminum fiber, with a diameter of 20 μm and a copper layer thickness of approximately 2 μm.
[0154] 1.4 Positive and negative current collector-active electrode composite fiber: A positive electrode and a negative electrode active material fiber were twisted and plied with the above current collector fiber using a two-for-one twister to prepare a positive electrode and a negative electrode current collector-active electrode composite fiber, respectively, with a twist of 500 twists / m.
[0155] 1.5 Diaphragm material fiber Material: Polypropylene (PP) fiber.
[0156] Preparation method: PP was dissolved in a mixed solvent of dichloromethane and ethanol to form a spinning solution with a PP concentration of 5wt% (the volume ratio of dichloromethane to ethanol was 7:3). Using electrospinning technology, the voltage was set to 15kV, the spinning rate was 0.5mL / h, and the collection distance was 20cm. After spinning, the fiber was dried at 60℃ for 6h.
[0157] 1.6 Electrolyte Materials Materials: 1M NaClO4 / EC / PC electrolyte solution, the volume ratio of ethylene carbonate (EC) and propylene carbonate (PC) is 1:1.
[0158] Preparation method: In a nitrogen environment, NaClO4, EC and PC are mixed and stirred for 4 hours until they are completely dissolved to obtain a NaClO4 / EC / PC electrolyte solution with a NaClO4 concentration of 1 mol / L.
[0159] 1.7 Support material fiber: Material: Aramid fiber, diameter about 50μm.
[0160] 2. Preparation and assembly of fiber energy storage devices based on sodium ion batteries 2.1 Preparation of inner braided positive electrode Material configuration: 6 positive electrode active material fibers and 2 nickel-plated carbon fibers.
[0161] Weaving process: Use 8 circular weaving machines to evenly distribute 6 positive current collector-active electrode composite fibers and 2 supporting material fibers on the weaving shuttle; set the weaving speed to 30r / min and maintain constant tension; during the weaving process, adjust the fiber tension regularly to ensure that the diameter of the braided tube is uniform; after weaving, dry the obtained inner braided tube in a vacuum drying oven at 80°C for 4h to remove residual solvent and obtain the inner braided positive electrode.
[0162] 2.2 Preparation of the intermediate diaphragm layer Material configuration: PP diaphragm fiber (6 pieces), aramid fiber (2 pieces).
[0163] Weaving process: Using the 8-circle weaving process, 6 PP diaphragm fibers and 2 aramid fibers are evenly woven on the surface of the inner braided positive electrode to form an intermediate braided tube with a thickness of about 100μm; during the weaving process, a constant speed (20r / min) and a tension of 0.5N are maintained to avoid the fibers being too tight or too loose to ensure uniform porosity of the diaphragm. After weaving, the intermediate braided tube is dried in a vacuum environment at 50℃ for 4h to obtain the intermediate diaphragm layer.
[0164] 2.3 Preparation of outer braided negative electrode Material configuration: 6 negative current collector-active electrode composite fibers and 2 aramid support fibers.
[0165] Weaving process: Use 8 circular weaving machines to evenly distribute 6 negative current collector-active electrode composite fibers and 2 supporting material fibers on the shuttle; during the weaving process, the middle separator layer is used as the core material for coating, and the weaving speed is maintained at 20r / min to ensure that the outer braided tube is tightly combined with the middle layer; during the weaving process, the weaving state of each layer is checked regularly to prevent the electrode material from being delaminated or piled up. After weaving, the outer braided tube is dried in a vacuum environment at 80℃ for 4h to remove residual solvent and moisture, and the outer braided negative electrode is obtained.
[0166] 2.4 Electrolyte impregnation and packaging Electrolyte impregnation: Immerse the woven multi-layer braided tube in 1M NaClO4 / EC / PC electrolyte solution and let it stand for 30 minutes to allow the electrolyte to be evenly impregnated into the multi-layer braided tube; during the impregnation process, gently stir the solution to ensure that the electrolyte is evenly distributed.
[0167] Electrode packaging: In a nitrogen environment, the positive and negative current collector fibers are welded to the electrode leads (copper foil and aluminum foil); epoxy resin is used to seal the electrode connection points to prevent electrolyte leakage.
[0168] Overall packaging: Use polytetrafluoroethylene (PTFE) heat shrink tubing to cover the outer surface of the device to form a complete sealing protective layer.
[0169] 3. Performance testing and characterization of fiber energy storage devices based on sodium ion batteries Specific capacity test: At a charge and discharge rate of 0.1C, the specific capacity of the device was measured to be 120mAh / g.
[0170] Rate performance test: Charge and discharge tests were carried out at different rates of 1C and 5C. The capacity retention rate was 95% at 1C and 75% at 5C.
[0171] Cycle life test: After 800 charge and discharge cycles at a rate of 0.5C, the capacity retention rate is 88%.
[0172] Mechanical properties test: After 500 bending tests at a bending radius of 15 mm, the device's capacity retention rate is 95%.
[0173] Example 4: Fiber energy storage device based on lithium-ion battery 1. Material Preparation 1.1 Positive electrode active material fiber Active material: Lithium iron phosphate (LiFePO4) nanoparticles.
[0174] Conductive additive: Carbon nanotubes (CNTs).
[0175] Binder: polyvinylidene fluoride (PVDF).
[0176] Preparation method: LiFePO4, CNT and PVDF were mixed in a mass ratio of 80:10:10, N-methylpyrrolidone (NMP) solvent was added, and stirred for 4 hours until the slurry was uniform (the concentration of LiFePO4 in the slurry was 8wt%). The slurry was loaded into an electrospinning machine, and the spinning voltage was set to 20kV, the spinning rate was 0.5mL / h, and the collection distance was 15cm. During the spinning process, the ambient temperature was controlled at 25°C and the humidity was less than 40%. After obtaining fibers with a diameter of about 200~300nm, the fibers were dried in a vacuum drying oven at 80°C for 12 hours to remove the solvent.
[0177] 1.2 Negative electrode active material fiber Active material: Composite material of graphite and silicon nanoparticles.
[0178] Conductive additive: carbon black.
[0179] Binder: polyvinylidene fluoride (PVDF).
[0180] Preparation method: Graphite, silicon particles and carbon black were mixed in a mass ratio of 50:20:10, PVDF was added as a binder, and NMP solvent was added to form a slurry (the concentration of graphite in the slurry was 5wt%, and the concentration of PVDF was 12%). Electrospinning was performed using an electrospinning process, with a spinning voltage of 18kV, a spinning rate of 0.5mL / h, and a collection distance of 18cm. After spinning, the fiber was dried in a vacuum drying oven at 80℃ for 6h.
[0181] 1.3 Fluid Collector Fiber Positive electrode current collector fiber: nickel-plated copper fiber, with a diameter of 20 μm and a nickel layer thickness of about 2 μm.
[0182] Negative electrode current collector fiber: copper-coated aluminum fiber, with a diameter of 20 μm and a copper layer thickness of approximately 2 μm.
[0183] Treatment method: Use an ultrasonic cleaner to clean in acetone for 10 minutes to remove surface impurities, then clean with deionized water, and finally dry in a vacuum drying oven at 60°C for 2 hours.
[0184] 1.4 Positive and negative current collector-active electrode composite fiber: A positive electrode and a negative electrode active material fiber were twisted and plied with the above current collector fiber using a two-for-one twister to prepare a positive electrode and a negative electrode current collector-active electrode composite fiber, respectively, with a twist of 500 twists / m.
[0185] 1.5 Diaphragm material fiber Material: Polypropylene (PP).
[0186] Preparation method: Dissolve polypropylene particles in dichloromethane and stir for 2 hours until completely dissolved to obtain a PP solution with a concentration of 5wt%. Use electrospinning technology for spinning, with a spinning voltage of 15kV, a spinning rate of 0.5mL / h, and a collection distance of 20cm to obtain PP diaphragm material fibers with a diameter of about 500nm.
[0187] 1.6 Electrolyte Materials Materials: 1M LiPF6 / EC / DMC electrolyte solution, the volume ratio of ethylene carbonate (EC) and dimethyl carbonate (DMC) is 1:1.
[0188] Preparation method: LiPF6, EC and DMC were mixed and stirred for 6 h in an inert gas (argon) to ensure complete dissolution and homogeneity to obtain a 1 M LiPF6 / EC / DMC electrolyte solution.
[0189] 1.7 Support material fiber: Material: Aramid fiber, diameter about 50μm.
[0190] 2. Preparation and assembly of fiber energy storage devices based on lithium-ion batteries 2.1 Preparation of inner braided positive electrode Material configuration: 6 positive current collector-active electrode composite fibers and 2 supporting fibers.
[0191] Weaving process: Use 8 circular weaving machines to evenly distribute 6 positive current collector-active electrode composite fibers and 2 support fibers on the weaving shuttle, set the weaving speed to 30r / min, maintain a constant tension of about 0.5N, ensure the uniform diameter of the braided tube, avoid fiber knotting or overlapping, and obtain an inner braided tube with a diameter of about 0.5mm. After weaving, the inner braided tube is dried in a vacuum drying oven at 80℃ for 6h to remove residual solvent and obtain the inner braided positive electrode.
[0192] 2.2 Preparation of the intermediate diaphragm layer Material configuration: PP diaphragm material fibers (6 pieces), supporting material fibers.
[0193] Weaving process: Using the same 8-circle weaving process, 6 PP material separator fibers and 2 support material fibers are evenly woven on the surface of the inner braided positive electrode to form a middle separator layer with a thickness of about 100μm; during the weaving process, a constant speed (25r / min) and a tension of 0.5N are maintained to avoid the fibers being too tight or too loose, thereby affecting the porosity and mechanical properties of the separator. After weaving, the middle layer separator fibers are placed in a vacuum environment at 50°C and dried for 4h.
[0194] 2.3 Preparation of outer braided negative electrode Material configuration: 6 negative current collector-active electrode composite fibers and 2 supporting fibers.
[0195] Weaving process: Use 8 circular weaving machines to evenly distribute 6 negative current collector-active electrode composite fibers and 2 support fibers on the shuttle; during the weaving process, the middle layer separator fiber is used as the core material for coating, and the weaving speed is maintained at 25r / min to ensure that the outer layer braided tube is tightly combined with the middle layer; during the weaving process, the weaving state of each layer is checked regularly to prevent the electrode material from being delaminated or piled up. After weaving, the outer layer braided tube is dried in a vacuum environment at 80℃ for 4h to remove residual solvent and moisture.
[0196] 2.4 Electrolyte impregnation and packaging Electrolyte impregnation: Immerse the woven multi-layer braided tube into 1M LiPF6 / EC / DMC electrolyte solution and let it stand for 30 minutes to allow the electrolyte to be evenly impregnated into the multi-layer braided tube; during the impregnation process, gently stir the solution to ensure uniform distribution of the electrolyte.
[0197] Electrode packaging: In an inert gas (argon) environment, the positive and negative current collector fibers are welded to the electrode leads (copper foil and aluminum foil); epoxy resin is used to seal the electrode connection points to prevent electrolyte leakage.
[0198] Overall packaging: Use polytetrafluoroethylene (PTFE) heat shrink tubing to cover the outer surface of the device to form a complete sealing protective layer.
[0199] 3. Performance testing and characterization of fiber energy storage devices based on lithium-ion batteries Specific capacity test: At a charge and discharge rate of 0.1C, the specific capacity of the device was measured to be 160mAh / g.
[0200] Rate performance test: Charge and discharge tests were carried out at different rates of 1C and 5C. It was found that the capacity retention rate was 95% at 1C and 80% at 5C.
[0201] Cycle life test: After 1000 charge and discharge cycles at 0.5C rate, the device’s capacity retention rate was 90%, demonstrating its good cycle stability.
[0202] Mechanical properties test: After 500 bending tests at a bending radius of 10 mm, the device's capacity retention rate was 98%.
[0203] Example 5: Fiber energy storage device based on zinc-air battery 1. Material Preparation 1.1 Positive electrode active material fiber Active materials: Manganese oxide (MnO2) and multi-walled carbon nanotubes (MWCNTs) composites.
[0204] Binder: polyvinylidene fluoride (PVDF).
[0205] Conductive agent: graphene nanosheets.
[0206] Preparation method: MnO2, MWCNTs and graphene nanosheets were mixed in a mass ratio of 50:20:10, PVDF powder was added as a binder, dissolved in N-methylpyrrolidone (NMP), and stirred for 4 hours to form a uniform slurry (the concentration of MnO2 in the slurry was 5wt%, and the concentration of PVDF was 12wt%). The slurry was loaded into an electrospinning machine, and the spinning voltage was set to 18kV, the spinning rate was 0.4mL / h, and the collection distance was 15cm to prepare positive electrode active material fibers with a diameter of about 200nm. After preparation, the fibers were dried in a vacuum environment at 80℃ for 8h.
[0207] 1.2 Negative electrode active material fiber Active materials: Zinc nanoparticles (Zn) and carbon nanotubes (CNT) composites.
[0208] Binder: Sodium carboxymethyl cellulose (CMC).
[0209] Preparation method: Mix zinc nanoparticles (particle size 50nm), CNT and CMC in a mass ratio of 5:1:4, add deionized water, stir until a uniform slurry state (the concentration of zinc nanoparticles in the slurry is 5wt%), load the resulting slurry into an electrospinning machine, set the spinning voltage to 15kV, the spinning rate to 0.5mL / h, and the collection distance to 20cm, and prepare negative electrode active material fibers with a diameter of about 300nm. After spinning, the fibers were dried in a vacuum drying oven at 60°C for 6h.
[0210] 1.3 Fluid Collector Fiber Positive electrode current collector fiber: gold-plated stainless steel fiber, 20 μm in diameter, 15 cm in length, and the thickness of the gold layer is about 2 μm.
[0211] Negative electrode current collector fiber: copper-plated carbon fiber, with a diameter of 20 μm, a length of 15 cm, and a copper layer thickness of approximately 2~3 μm.
[0212] Treatment method: Use acetone and deionized water to ultrasonically clean the current collector fiber for 10 minutes each, and then dry it in a vacuum drying oven at 60°C for 2 hours.
[0213] 1.4 Positive and negative current collector-active electrode composite fiber: A positive electrode and a negative electrode active material fiber were twisted and plied with the above current collector fiber using a two-for-one twister to prepare a positive electrode and a negative electrode current collector-active electrode composite fiber, respectively, with a twist of 500 twists / m.
[0214] 1.5 Diaphragm material fiber Material: Polyethylene (PE) fiber.
[0215] Preparation method: Dissolve polyethylene particles in dichloromethane to form a spinning solution with a concentration of 5wt%. Use electrospinning technology for spinning, set the voltage to 15kV, the spinning rate to 0.5mL / h, and the collection distance to 18cm. After preparing PE fibers with a diameter of about 300nm, dry them at 50℃ for 4h.
[0216] 1.6 Electrolyte Materials Materials: 6M KOH aqueous solution.
[0217] Preparation method: In an inert gas environment, potassium hydroxide is dissolved in deionized water and stirred until completely dissolved to obtain a 6M KOH aqueous solution. After the preparation is completed, the electrolyte solution is stored in an inert gas environment to prevent moisture absorption and carbonation.
[0218] 1.7 Support Fiber: Polytetrafluoroethylene fiber, diameter about 50μm.
[0219] 2. Preparation and assembly of fiber energy storage devices based on zinc-air batteries 2.1 Preparation of inner braided positive electrode Material configuration: 6 positive current collector-active electrode composite fibers and 2 supporting fibers.
[0220] Weaving process: Use 8 circular weaving machines to evenly distribute 6 positive current collector-active electrode composite fibers and 2 supporting fibers on the weaving shuttle; set the weaving speed to 30r / min, maintain a constant tension of about 0.25N, ensure that the diameter of the braided tube is uniform, and avoid fiber knotting or overlapping; after weaving, dry the obtained inner braided tube in a vacuum drying oven at 80°C for 6h to remove residual solvent and obtain the inner braided positive electrode.
[0221] 2.2 Preparation of the intermediate diaphragm layer Material configuration: PE diaphragm fibers (6 pieces), supporting material fibers (2 pieces).
[0222] Weaving process: Using the same 8-circle weaving process, the PE diaphragm fibers and support fibers are evenly woven on the surface of the inner braided positive electrode to form a middle diaphragm layer with a thickness of about 100μm; during the weaving process, a constant speed (25r / min) and tension are maintained to avoid the fibers being too tight or too loose to ensure uniform diaphragm porosity. After weaving, the middle diaphragm layer is dried in a vacuum environment at 50℃ for 4h.
[0223] 2.3 Preparation of outer braided negative electrode Material configuration: 6 negative current collector-active electrode composite fibers and 2 supporting fibers.
[0224] Weaving process: Use 8 circular weaving machines to evenly distribute 6 current collector-active electrode composite fibers and 2 support fibers on the shuttle; during the weaving process, the middle diaphragm layer is used as the core material for coating, and the weaving speed is maintained at 25r / min to ensure that the outer braided tube is tightly combined with the middle layer; during the weaving process, the weaving state of each layer is checked regularly to prevent the electrode material from being delaminated or piled up. After weaving, the outer braided tube is dried in a vacuum environment at 80℃ for 4h to remove residual solvent and moisture.
[0225] 2.4 Electrolyte impregnation and packaging Electrolyte impregnation: The woven multi-layer braided tube is immersed in a 6M KOH aqueous solution and vacuum impregnated for 30 minutes to ensure that the electrolyte is evenly impregnated into the diaphragm layer.
[0226] Electrode packaging: In a nitrogen environment, the positive and negative current collector fibers are welded to the electrode leads (copper wires) respectively; epoxy resin is used to seal the electrode connection points to prevent electrolyte leakage.
[0227] Overall packaging: Use polytetrafluoroethylene (PTFE) heat shrink tubing to cover the outer surface of the device to form a complete sealing protective layer.
[0228] 3. Performance testing and characterization of fiber energy storage devices based on zinc-air batteries Specific capacity test: At a charge and discharge rate of 0.1C, the specific capacity of the device was measured to be 350mAh / g.
[0229] Rate performance test: Charge and discharge tests were carried out at different rates of 1C and 5C. The capacity retention rate was 92% at 1C and 70% at 5C.
[0230] Cycle life test: After 1000 charge and discharge cycles at 0.5C rate, the capacity retention rate is 85%.
[0231] Mechanical properties test: After 1000 bending tests at a bending radius of 15mm, the device's capacity retention rate is 90%.
[0232] Example 6: Fiber energy storage device based on supercapacitor 1. Material Preparation 1.1 Positive electrode active material fiber Active materials: activated carbon (AC) and carbon nanotubes (CNTs) composites.
[0233] Conductive agent: graphene nanosheets.
[0234] Binder: polyvinylidene fluoride (PVDF).
[0235] Preparation method: Activated carbon, CNTs and graphene nanosheets were mixed in a mass ratio of 70:15:15, PVDF was added as a binder, dissolved in N-methylpyrrolidone (NMP), and stirred for 4 hours to form a uniform slurry (the concentration of activated carbon in the slurry was 3.5wt%, and the concentration of PVDF was 10wt%). The slurry was loaded into an electrospinning machine, and the spinning voltage was set to 20kV, the spinning rate was 0.5mL / h, and the collection distance was 15cm to prepare positive electrode active material fibers with a diameter of about 300nm. After spinning, the fibers were placed in a vacuum drying oven at 80℃ and dried for 8h.
[0236] 1.2 Negative electrode active material fiber Active materials: Reduced graphene oxide (rGO) and activated carbon (AC) composites.
[0237] Binder: polyvinylidene fluoride (PVDF).
[0238] Preparation method: Reduced graphene oxide (rGO), activated carbon and PVDF were mixed in a mass ratio of 4:1:5, dissolved in NMP, and stirred to a uniform slurry (the concentration of rGO in the slurry was 4wt%). The slurry was loaded into an electrospinning machine for spinning, and the spinning voltage was set to 15kV, the spinning rate was 0.5mL / h, and the collection distance was 18cm to prepare negative electrode active material fibers with a diameter of about 300nm. After spinning, the fibers were dried in a vacuum drying oven at 60℃ for 6h.
[0239] 1.3 Fluid Collector Fiber Positive electrode current collector fiber: stainless steel fiber, diameter 20μm.
[0240] Negative electrode current collector fiber: copper-plated carbon fiber, diameter 20μm, copper layer thickness 2~3μm.
[0241] Treatment method: Use an ultrasonic cleaner to clean the current collector fiber in acetone for 10 minutes to remove surface impurities, then wash it with deionized water, and then dry it in a vacuum drying oven at 60°C for 2 hours.
[0242] 1.4 Positive and negative current collector-active electrode composite fiber: A positive electrode and a negative electrode active material fiber were twisted and plied with the above current collector fiber using a two-for-one twister to prepare a positive electrode and a negative electrode current collector-active electrode composite fiber, respectively, with a twist of 500 twists / m.
[0243] 1.5 Diaphragm material fiber Material: Polyethersulfone (PES) fiber.
[0244] Preparation method: Dissolve polyethersulfone (PES) in a mixed solvent of dichloromethane and ethanol (volume ratio of 7:3) to obtain a spinning solution with a concentration of 5wt%. Use electrospinning technology for spinning, set the voltage to 15kV, the spinning rate to 0.5mL / h, and the collection distance to 20cm to prepare PES diaphragm material fibers with a diameter of about 300nm. After preparation, the fiber is placed in a vacuum environment at 50℃ and dried for 4h.
[0245] 1.6 Electrolyte Materials Materials: 1M TEABF4 / PC electrolyte solution.
[0246] Preparation method: In an inert gas environment, ethyltrimethylammonium tetrafluoroborate (TEABF4) is mixed with PC solvent and stirred for 6 hours until completely dissolved to obtain a 1M TEABF4 / PC electrolyte solution, which is set aside for later use.
[0247] 1.7 Support Fiber: Polytetrafluoroethylene fiber, diameter about 50μm.
[0248] 2. Preparation and assembly of fiber energy storage devices based on supercapacitors 2.1 Preparation of inner braided positive electrode Material configuration: 6 positive current collector-active electrode composite fibers and 2 supporting fibers.
[0249] Weaving process: Use 8 circular weaving machines to evenly distribute 6 positive current collector-active electrode composite fibers and 2 supporting fibers on the weaving shuttle; set the weaving speed to 30r / min, and maintain a constant tension of about 0.25N to prevent the fibers from knotting or overlapping; after weaving, dry the resulting inner braided tube in a vacuum drying oven at 80°C for 4h to remove residual solvent and obtain the inner braided positive electrode.
[0250] 2.2 Preparation of the intermediate diaphragm layer Material configuration: PES diaphragm material fibers (6 pieces).
[0251] Weaving process: Using the same 8-circle weaving process, the PES diaphragm fibers and support fibers are evenly woven on the surface of the inner braided positive electrode to form an intermediate braided tube with a thickness of about 100μm; during the weaving process, a constant speed (20r / min) and a tension of about 0.5N are maintained to ensure that the diaphragm fibers are evenly distributed and avoid being too loose or too tight. After the weaving is completed, the intermediate braided tube is dried in a vacuum environment at 50℃ for 4h to obtain the intermediate diaphragm layer.
[0252] 2.3. Preparation of outer braided negative electrode Material configuration: 6 negative current collector-active electrode composite fibers and 2 supporting fibers.
[0253] Weaving process: Use 8 circular weaving machines to evenly distribute 6 negative current collector-active electrode composite fibers and 2 supporting fibers on the shuttle; during the weaving process, the middle separator layer is used as the core material for coating, and the weaving speed is maintained at 20r / min to ensure that the outer braided tube is tightly combined with the middle layer; during the weaving process, the weaving state of each layer is checked regularly to prevent the electrode material from being delaminated or piled up. After weaving, the outer braided tube is dried in a vacuum environment at 80℃ for 4h to remove residual solvent and moisture.
[0254] 2.4 Electrolyte impregnation and packaging Electrolyte impregnation: Immerse the braided multilayer braided tube into 1M TEABF4 / PC electrolyte solution and let it stand for 30 minutes to ensure that the electrolyte is evenly immersed in the multilayer braided tube; in a vacuum environment, gently stir the solution to ensure that the electrolyte is evenly distributed.
[0255] Electrode packaging: In an inert gas environment, the positive and negative current collector fibers are welded to the electrode leads (copper wires); epoxy resin is used to seal the electrode connection points to prevent electrolyte leakage.
[0256] Overall packaging: Use polytetrafluoroethylene (PTFE) heat shrink tubing to cover the outer surface of the device to form a complete sealing protective layer.
[0257] 3. Performance testing and characterization of fiber energy storage devices based on supercapacitors Specific capacitance test: At a current density of 0.5 A / g, the specific capacitance of the device was measured to be 200 F / g.
[0258] Rate performance test: Charge and discharge tests were carried out at different current densities of 1A / g and 10A / g. The specific capacitance retention rate was 98% at 1A / g and 85% at 10A / g.
[0259] Cycle life test: After 5000 charge and discharge cycles at a current density of 1A / g, the device's specific capacitance retention rate is 95%.
[0260] Mechanical properties test: After 1000 bending tests at a bending radius of 10 mm, the device's specific capacitance retention rate was 92%.
[0261] Example 7: Fiber energy storage device based on dry cell 1. Material Preparation 1.1 Positive electrode active material fiber Active material: Manganese dioxide (MnO2) and graphite powder composite material.
[0262] Binder: polyvinylidene fluoride (PVDF).
[0263] Preparation method: MnO2, graphite powder and PVDF are mixed in a mass ratio of 4:1:5, N-methylpyrrolidone (NMP) solvent is added, and stirred for 4 hours to form a uniform slurry (the MnO2 concentration in the slurry is 4wt%). The slurry is loaded into an electrospinning machine for spinning, and the spinning voltage is set to 15kV, the spinning rate is 0.4mL / h, and the collection distance is 15cm. During the spinning process, the ambient temperature is maintained at 25°C and the humidity is controlled below 40%, and a positive electrode active material fiber with a diameter of about 300nm is obtained. After spinning, the fiber is placed in a vacuum drying oven at 80°C for 8 hours to ensure that the solvent is completely removed.
[0264] 1.2 Negative electrode active material fiber Active materials: Zinc powder (Zn) and carbon nanotube (CNT) composite materials.
[0265] Binder: Sodium carboxymethyl cellulose (CMC).
[0266] Preparation method: Mix zinc powder, CNT and CMC in a mass ratio of 5:1:4, add deionized water and stir to form a uniform slurry (Zn concentration in the slurry is 5wt%). Load the slurry into an electrospinning machine for spinning, set the spinning voltage to 12kV, the spinning rate to 0.5mL / h, and the collection distance to 20cm to prepare negative electrode active material fibers with a diameter of about 300nm. After spinning, the fibers were dried at 60℃ in a vacuum environment for 6h to remove moisture.
[0267] 1.3 Fluid Collector Fiber Positive electrode current collector fiber: nickel-plated copper fiber, 20 μm in diameter, 15 cm in length, and 2 μm in nickel layer thickness.
[0268] Negative electrode current collector fiber: copper-plated carbon fiber, diameter 20μm, length 15cm, copper layer thickness 2~3μm.
[0269] Treatment method: Use an ultrasonic cleaner to clean in acetone for 10 minutes to remove surface impurities, then clean with deionized water, and then dry in a vacuum drying oven at 60°C for 2 hours.
[0270] 1.4 Positive and negative current collector-active electrode composite fiber: A positive electrode and a negative electrode active material fiber were twisted and plied with the above current collector fiber using a two-for-one twister to prepare a positive electrode and a negative electrode current collector-active electrode composite fiber, respectively, with a twist of 500 twists / m.
[0271] 1.5 Diaphragm material fiber Material: Polyethylene (PE) / Polypropylene (PP) double-layer composite fiber.
[0272] Preparation method: PE and PP were dissolved in dichloromethane at a mass ratio of 50:50 to form a spinning solution with a total concentration of PE and PP of 5wt%. Electrospinning technology was used for spinning, with a voltage of 15kV, a spinning rate of 0.5mL / h, and a collection distance of 18cm. After spinning, the fiber was dried at 50℃ for 4h.
[0273] 1.6 Electrolyte Materials Materials: saturated NH4Cl / ZnCl2 mixed electrolyte solution.
[0274] Preparation method: In an inert gas environment, first dissolve ammonium chloride and zinc chloride in deionized water respectively, stir until completely dissolved, and obtain saturated NH4Cl solution and saturated zinc chloride solution. Mix the two solutions in a volume ratio of 1:1, and stir for 6 hours until uniform, to obtain a saturated NH4Cl / ZnCl2 mixed electrolyte solution. Store in a vacuum environment to prevent moisture absorption and water evaporation.
[0275] 1.7 Support Fiber: Polyimide fiber, diameter about 35μm.
[0276] 2. Preparation and assembly of fiber energy storage devices based on dry cells 2.1 Preparation of inner braided positive electrode Material configuration: 6 positive current collector-active electrode composite fibers and 2 supporting fibers.
[0277] Weaving process: Use 8 circular weaving machines to evenly distribute 6 positive current collector-active electrode composite fibers and 2 supporting fibers on the weaving shuttle; set the weaving speed to 30r / min and maintain a constant tension of about 0.25N; during the weaving process, regularly adjust the fiber tension to ensure that the diameter of the braided tube is uniform and to avoid fiber knotting or overlapping; after weaving, dry the resulting inner braided tube in a vacuum drying oven at 80°C for 6h to remove residual solvent and obtain the inner braided positive electrode.
[0278] 2.2 Preparation of the intermediate diaphragm layer Material configuration: PE / PP composite diaphragm fibers (6 pieces), support fibers (2 pieces).
[0279] Weaving process: Using the same 8-circle weaving process, the PE / PP diaphragm fibers and support fibers are evenly woven on the surface of the inner braided positive electrode to form an intermediate braided tube with a thickness of about 100μm; during the weaving process, a constant speed (20r / min) and tension are maintained to ensure that the diaphragm fibers are evenly distributed and avoid being too loose or too tight. After weaving, the intermediate braided tube is placed in a vacuum environment at 50°C and dried for 4 hours to obtain the intermediate diaphragm layer.
[0280] 2.3 Preparation of outer braided negative electrode (negative electrode layer braided tube) Material configuration: 6 negative current collector-active electrode composite fibers and 2 supporting fibers.
[0281] Weaving process: Use 8 circular weaving machines to evenly distribute 6 negative electrode current collector-active electrode composite fibers and 2 supporting fibers on the shuttle; during the weaving process, the middle separator layer is used as the core material for coating, and the weaving speed is maintained at 20r / min to ensure that the outer braided tube is tightly combined with the middle layer; during the weaving process, the weaving state of each layer is checked regularly to prevent the electrode material from being delaminated or piled up. After the weaving is completed, the outer braided tube is dried in a vacuum environment at 80℃ for 4h to remove residual solvent and moisture, and the outer braided negative electrode is obtained.
[0282] 2.4 Electrolyte impregnation and packaging Electrolyte impregnation: Immerse the woven multi-layer braided tube in a saturated NH4Cl / ZnCl2 mixed electrolyte solution and let it stand for 30 minutes to allow the electrolyte to evenly penetrate the multi-layer braided tube; gently stir the solution under a vacuum environment to ensure that the electrolyte is evenly distributed and fully penetrated.
[0283] Electrode packaging: In an inert gas environment, the positive and negative current collector fibers are welded to the electrode leads (copper foil and aluminum foil); epoxy resin is used to seal the electrode connection points to prevent electrolyte leakage.
[0284] Overall packaging: Use polytetrafluoroethylene (PTFE) heat shrink tubing to cover the outer surface of the device to form a complete sealing protective layer.
[0285] 3. Performance testing and characterization of fiber energy storage devices based on dry cells Specific capacity test: At a charge and discharge rate of 0.1C, the specific capacity of the device was measured to be 200mAh / g.
[0286] Rate performance test: Charge and discharge tests were carried out at different rates of 1C and 5C. The capacity retention rate was 92% at 1C and 70% at 5C.
[0287] Cycle life test: After 800 charge and discharge cycles at a rate of 0.5C, the capacity retention rate is 85%.
[0288] Mechanical properties test: After 500 bending tests at a bending radius of 10 mm, the device's capacity retention rate was 92%.
[0289] Example 8: Composite fiber energy storage device based on multiple energy storage methods (preparation flow chart see Figure 3 ) Composite energy storage devices take advantage of the fiber braiding structure to integrate multiple energy storage units such as lithium-ion batteries, sodium-ion batteries, zinc-air batteries and supercapacitors into a multi-layer fiber braided tube structure. Each energy storage unit is stacked in sequence, and through the layered braiding design, multiple energy storage units can be effectively connected in series and in parallel. This integrated solution can meet different electrochemical requirements at the same time and realize flexible combination and dynamic adjustment of energy storage mechanisms.
[0290] 1. Specific material selection 1.1 Lithium-ion battery cell Positive electrode active material fiber: lithium iron phosphate (LiFePO4) and carbon nanotube (CNT) composite material.
[0291] Negative electrode active material fibers: graphene and silicon nanoparticle composites.
[0292] Diaphragm material fiber: polypropylene (PP) fiber.
[0293] Positive electrode current collector fiber: nickel-plated copper fiber, diameter 20μm, nickel layer thickness 2μm; Negative electrode current collector fiber: copper-coated aluminum fiber, diameter 20μm, copper layer thickness 2μm.
[0294] Electrolyte: 1M LiPF6 / EC / DMC electrolyte solution, the volume ratio of EC to DMC is 1:1.
[0295] 1.2 Sodium-ion battery cell Positive electrode active material fiber: layered sodium manganese oxide (Na 0.44 MnO2) nanoparticles and carbon nanotubes (CNTs) composites.
[0296] Negative electrode active material fiber: hard carbon fiber.
[0297] Diaphragm material fiber: polypropylene (PP) fiber.
[0298] Positive electrode current collector material: nickel-plated carbon fiber, diameter 20μm, nickel layer thickness 2~3μm.
[0299] Negative electrode current collector material: copper-coated aluminum fiber, diameter 20μm, copper layer thickness 2μm.
[0300] Electrolyte: 1M NaClO4 / PC / EC electrolyte solution, the volume ratio of solvent EC to PC is 1:1.
[0301] 1.3 Zinc-air battery cell Positive electrode active material fiber: manganese oxide (MnO2) and carbon nanotube composite fiber.
[0302] Negative electrode active material fiber: zinc powder and graphene composite fiber.
[0303] Diaphragm material fiber: polyethylene (PE) fiber.
[0304] Positive electrode current collector fiber: gold-plated stainless steel fiber, diameter 20μm, gold layer thickness 2μm.
[0305] Negative electrode current collector fiber: copper-plated carbon fiber, diameter 20μm, copper layer thickness 2~3μm.
[0306] Electrolyte solution: 6 M KOH aqueous solution.
[0307] 1.4 Supercapacitor Unit Positive electrode active material fiber: activated carbon (AC) and graphene composite material.
[0308] Negative electrode active material fibers: reduced graphene oxide (rGO) and activated carbon composites.
[0309] Diaphragm material fiber: polyethersulfone (PES) fiber.
[0310] Positive electrode current collector material: gold-plated stainless steel fiber, diameter 20μm, gold layer thickness 2μm.
[0311] Negative electrode current collector fiber: copper-coated carbon fiber, diameter 20μm, copper layer thickness 2μm.
[0312] Electrolyte solution: 1M TEABF4 / PC electrolyte solution.
[0313] 1.5 Protection layer Polytetrafluoroethylene (PTFE) fiber, 50 μm in diameter.
[0314] 1.6 Support Fiber Polytetrafluoroethylene (PTFE) fiber, 35 μm in diameter.
[0315] 2. Preparation and assembly of composite fiber energy storage devices based on various energy storage methods 2.1 First layer: lithium-ion battery cells (innermost layer) Material configuration: 6 positive current collector-active electrode composite fibers, 6 negative current collector-active electrode composite fibers, 6 separator fibers, and 6 support fibers.
[0316] Weaving process: Using 8 circular weaving machines, weave 6 positive electrode current collector-active electrode composite fibers and 2 supporting fibers to form an inner layer of braided positive electrode; weave 6 diaphragm material fibers and 2 supporting materials on the outside of the inner layer of braided positive electrode to form a diaphragm layer, and weave 6 negative electrode current collector-active electrode composite fibers and 2 supporting fibers on the surface of the diaphragm layer to form an outer layer of braided negative electrode to obtain an inner layer of lithium-ion battery tube; the weaving speed is set to 20r / min to maintain uniform fiber tension and prevent fiber crossing and twisting. After weaving, the inner layer of lithium-ion battery tube is dried in a vacuum environment at 80℃ for 6h to ensure that the solvent is completely removed to obtain a lithium-ion battery unit.
[0317] Electrolyte impregnation: Immerse the woven multi-layer braided tube into the electrolyte solution of the lithium-ion battery and let it stand for 30 minutes to allow the electrolyte to evenly penetrate the multi-layer braided tube.
[0318] Preparation of the first protective layer: Weaving the first protective layer on the surface of the lithium-ion battery cell, using an 8-spindle circular knitting machine at a speed of 25r / min to tightly weave 8 PTFE fibers outside the lithium-ion battery cell.
[0319] 2.2 Second layer: sodium-ion battery cells (coated on the outside of lithium-ion battery cells) Material configuration: 6 sodium ion positive current collector-active electrode composite fibers, 6 sodium ion negative current collector-active electrode composite fibers, 6 separator fibers, and 6 support fibers.
[0320] Weaving process: According to the weaving process of 2.1, the inner layer of the positive electrode, the separator layer and the outer layer of the negative electrode are sequentially weaved on the surface of the lithium-ion battery cell, and dried to obtain a sodium-ion battery cell; a constant tension is maintained during the weaving process to ensure that the fibers are arranged neatly and to avoid accumulation or overlap of material fibers.
[0321] Electrolyte impregnation: The woven multi-layer braided tube of the sodium ion battery is immersed in the electrolyte solution of the sodium ion battery and allowed to stand for 30 minutes to allow the electrolyte to be evenly impregnated into the multi-layer braided tube.
[0322] Preparation of the second protective layer: Weaving the second protective layer on the surface of the sodium-ion battery cell, using an 8-spindle circular knitting machine at a speed of 25r / min to tightly weave 8 PTFE fibers outside the lithium-ion battery cell.
[0323] 2.3 The third layer: zinc-air battery cells (coated on the outside of the sodium-ion battery cells) Material configuration: 6 MnO2 positive current collector-active electrode composite fibers, 6 zinc powder negative current collector-active electrode composite fibers, 6 separator fibers, and 6 support fibers.
[0324] Weaving process: According to the weaving process of 2.1, the inner layer of the positive electrode, the separator layer and the outer layer of the negative electrode are weaved in sequence on the surface of the sodium ion battery unit, and vacuum dried at 70°C for 4 hours to obtain a zinc-air battery unit; the weaving speed is set to 15r / min to avoid fiber knotting or sliding and ensure close contact between layers.
[0325] Electrolyte impregnation: The multi-layer braided tube of the zinc-air battery is immersed in the electrolyte solution of the zinc-air battery and allowed to stand for 30 minutes to allow the electrolyte to be evenly impregnated into the multi-layer braided tube.
[0326] Preparation of the third protective layer: The third protective layer is woven on the surface of the zinc-air battery unit. A 16-spindle circular knitting machine is used at a speed of 20 r / min to tightly weave 16 PTFE fibers outside the lithium-ion battery unit.
[0327] 2.4 Fourth layer: supercapacitor unit (outer layer) Material configuration: 6 activated carbon positive current collector-active electrode composite fibers, 6 reduced graphene oxide (rGO) negative current collector-active electrode composite fibers, 6 separator fibers, and 6 support fibers.
[0328] Weaving process: According to the weaving process of 2.1, the inner layer of the positive electrode, the separator layer and the outer layer of the negative electrode are woven in sequence on the surface of the zinc-air battery unit, and vacuum dried at 70°C for 6h to obtain a supercapacitor unit.
[0329] Electrolyte impregnation: The multi-layer braided tube of the supercapacitor is immersed in the electrolyte solution of the zinc-air battery and allowed to stand for 30 minutes to allow the electrolyte to be evenly impregnated into the multi-layer braided tube.
[0330] Preparation of the fourth protective layer: The fourth protective layer is woven on the surface of the supercapacitor unit. A 16-spindle circular knitting machine is used at a speed of 25 r / min to tightly weave 16 PTFE fibers outside the lithium-ion battery unit.
[0331] 2.5 Packaging Electrode packaging: Connect the electrode current collectors at each layer in an inert gas environment and connect them in series or parallel according to the energy storage mode.
[0332] Overall packaging: Use PTFE heat shrink tubing to seal the entire device to form a complete composite energy storage fiber structure.
[0333] 3. Performance testing and characterization of composite fiber energy storage devices based on various energy storage methods Electrochemical performance test: At a charge and discharge rate of 0.1C, the specific capacity of the device was measured to be 280mAh / g in full parallel mode, and 220mAh / g in full series mode.
[0334] Cycle life test: After 1000 charge and discharge cycles at 0.5C, the average capacity retention rate in full parallel mode is 85%, and the capacity retention rate in full series mode is 88%.
[0335] Mechanical properties test: 1000 bending cycle tests were carried out with a bending radius of 5mm, and the capacity retention rates in both series and parallel modes exceeded 90%.
[0336] Example 9: Series-parallel connection design of multilayer energy storage units of composite fiber energy storage device based on multilayer energy storage unit series-parallel structure (preparation flow chart see Figure 3 ) This embodiment realizes the series and parallel connection between different energy storage units (lithium-ion batteries, sodium-ion batteries, supercapacitors, zinc-air batteries) through the design of multi-layer fiber braided structure. By precisely controlling the current collector position and wire connection points of different energy storage units, a specific electrochemical performance combination can be formed in the multifunctional composite energy storage device to meet the needs of various application scenarios.
[0337] Design ideas: Series connection: Different energy storage units (such as lithium-ion batteries and zinc-air batteries) are directly connected through current collectors and wires to form a series structure to achieve voltage superposition and improvement, which is suitable for scenarios with high voltage output requirements.
[0338] Parallel connection: Two or more energy storage units (such as supercapacitor units and sodium-ion battery units) are connected in parallel through current collector materials and wires to increase the overall capacity and power density, which is suitable for application scenarios where large currents are released instantaneously.
[0339] 1. Specific material selection 1.1 Lithium-ion battery cell (layer L1) Positive electrode active material fiber: LiFePO4 and carbon nanotube (CNT) composite fiber.
[0340] Negative electrode active material fiber: graphene and silicon nanoparticle composite fiber.
[0341] Diaphragm material fiber: polypropylene (PP) fiber.
[0342] Current collector fibers: nickel-plated copper fibers (positive electrode current collector fibers) and copper-plated aluminum fibers (negative electrode current collector fibers), with a diameter of 20 μm.
[0343] Electrolyte: 1M LiPF6 / EC / DMC electrolyte, the volume ratio of EC to DMC is 1:1.
[0344] 1.2 Sodium-ion battery cell (layer L2) Positive electrode active material fiber: Na0.44MnO2 and carbon nanotube (CNTs) composite fiber.
[0345] Negative electrode active material fiber: hard carbon fiber.
[0346] Diaphragm material fiber: polypropylene (PP) fiber.
[0347] Current collector materials: nickel-plated carbon fiber (positive electrode current collector fiber) and copper-plated aluminum fiber (negative electrode current collector fiber), with a diameter of 20μm.
[0348] Electrolyte: 1M NaClO4 / PC / EC electrolyte solution, the volume ratio of EC to PC is 1:1.
[0349] 1.3 Supercapacitor unit (Layer L3) Positive electrode active material fiber: activated carbon (AC) and graphene composite fiber.
[0350] Negative electrode active material fibers: reduced graphene oxide (rGO) and activated carbon composite fibers.
[0351] Diaphragm material fiber: polyethersulfone (PES) fiber.
[0352] Current collector materials: gold-plated stainless steel fibers (positive electrode current collector fibers) and copper-plated carbon fibers (negative electrode current collector fibers), with a diameter of 20 μm.
[0353] Electrolyte: 1M TEABF4 / PC electrolyte solution.
[0354] 1.4 zinc-air battery cells (layer L4) Positive electrode active material fiber: MnO2 and graphene composite fiber.
[0355] Negative electrode active material fibers: zinc powder and carbon fiber composite fibers.
[0356] Diaphragm material fiber: polyethylene (PE) fiber.
[0357] Current collector materials: gold-plated stainless steel fiber (positive electrode current collector fiber) and copper-plated carbon fiber (negative electrode current collector fiber), with a diameter of 20 μm.
[0358] Electrolyte: 6M KOH aqueous solution.
[0359] 1.5 Protection layer Polytetrafluoroethylene (PTFE) fiber, 50 μm in diameter.
[0360] 1.6 Support Fiber Polytetrafluoroethylene (PTFE) fiber, 35 μm in diameter.
[0361] 2. Preparation and Assembly of Composite Devices Prepare according to the method of Example 8.
[0362] 2.1 Step 1: Preparation and series connection of lithium-ion battery cells (L1 layer) Using the 8-circle weaving process, the 6 positive electrode current collector-active electrode composite fibers of the lithium-ion battery are mixed and woven with 2 supporting fibers to form the inner layer of the braided positive electrode. The 6 diaphragm material fibers and 2 supporting fibers are woven on the outside of the inner layer of the braided positive electrode to form the diaphragm layer, and the 6 lithium-ion negative electrode current collector-active electrode composite fibers are mixed and woven with 2 supporting fibers on the surface of the diaphragm layer to form the L1 layer lithium-ion battery unit.
[0363] Series connection design: Connect the copper foil lead (positive electrode) and the aluminum foil lead (negative electrode) at both ends of the L1 layer. Connect the negative electrode lead of the lithium-ion battery L1 layer to the positive electrode lead of the sodium-ion battery L2 layer through a conductive copper wire to form a series relationship.
[0364] Electrolyte impregnation: Immerse the woven multi-layer braided tube into the electrolyte solution of the lithium-ion battery and let it stand for 30 minutes to allow the electrolyte to evenly penetrate the multi-layer braided tube.
[0365] Preparation of the first protective layer: Weaving the first protective layer on the surface of the lithium-ion battery cell, using an 8-spindle circular knitting machine at a speed of 30r / min to tightly weave 8 PTFE fibers outside the lithium-ion battery cell.
[0366] 2.2 Step 2: Sodium-ion battery unit (L2 layer) and parallel connection design Using the 8-wire weaving process, the 6 positive electrode current collector-active electrode composite fibers of the sodium ion battery are mixed and woven with 2 supporting fibers to form the inner layer of the braided positive electrode. The 6 diaphragm material fibers and 2 supporting fibers are woven on the outside of the inner layer of the braided positive electrode to form the diaphragm layer, and the 6 sodium ion negative electrode current collector-active electrode composite fibers are mixed and woven with 2 supporting fibers on the surface of the diaphragm layer to form the L2 layer of the sodium ion battery unit.
[0367] Parallel connection design: Connect copper foil leads (positive electrode) and aluminum foil leads (negative electrode) to the positive and negative ends of the L2 layer respectively. Connect the L2 layer in parallel with another sodium-ion battery cell through the current collector material (copper-coated carbon fiber) to improve the overall current output capacity.
[0368] Electrolyte impregnation: The woven multi-layer braided tube of the sodium ion battery is immersed in the electrolyte solution of the sodium ion battery and allowed to stand for 30 minutes to allow the electrolyte to be evenly impregnated into the multi-layer braided tube.
[0369] Preparation of the second protective layer: Weaving the second protective layer on the surface of the sodium-ion battery cell, using an 8-spindle circular knitting machine at a speed of 30r / min to tightly weave 8 PTFE fibers outside the lithium-ion battery cell.
[0370] 2.3 Step 3: Preparation and parallel design of supercapacitor units (L3 layer) Using the 12-circle weaving process, the activated carbon positive electrode current collector-active electrode composite fiber of the supercapacitor is mixed and woven with the support fiber to form the inner layer of the braided positive electrode. 12 diaphragm material fibers and 4 support fibers are woven on the outside of the inner layer of the braided positive electrode to form a diaphragm layer, and the rGO negative electrode current collector-active electrode composite fiber and the support fiber are mixed and woven on the surface of the diaphragm layer to form the L3 layer supercapacitor unit.
[0371] Parallel connection design: The positive and negative electrodes of the L3 layer supercapacitor are respectively connected in parallel with the positive and negative electrodes of the L2 layer sodium-ion battery through gold-plated stainless steel fibers to form a large-capacity capacitor structure.
[0372] Electrolyte impregnation: The multi-layer braided tube of the supercapacitor is immersed in the electrolyte solution of the zinc-air battery and allowed to stand for 30 minutes to allow the electrolyte to be evenly impregnated into the multi-layer braided tube.
[0373] Preparation of the third protective layer: Weaving the third protective layer on the surface of the supercapacitor unit, using an 8-spindle circular knitting machine at a speed of 30r / min to tightly weave 8 PTFE fibers outside the lithium-ion battery unit.
[0374] 2.4 Step 4: Preparation and series design of zinc-air battery unit (L4 layer) Using the 8-wire weaving process, the positive electrode current collector-active electrode composite fibers and supporting fibers of the zinc-air battery are mixed and woven to form an inner layer of braided positive electrode, 6 diaphragm material fibers and 2 supporting fibers are woven on the outside of the inner layer of braided positive electrode to form a diaphragm layer, and the negative electrode current collector-active electrode composite fibers and supporting fibers are mixed and woven on the surface of the diaphragm layer to form an outer layer of braided negative electrode, forming an L4-layer zinc-air battery unit.
[0375] Series connection design: The positive lead of the L4 layer zinc-air battery is connected to the negative lead of the L3 layer supercapacitor to form a series relationship, thereby increasing the overall output voltage, and the negative electrode of L4 serves as the negative electrode output of the entire device.
[0376] Electrolyte impregnation: The multi-layer braided tube of the zinc-air battery is immersed in the electrolyte solution of the zinc-air battery and allowed to stand for 30 minutes to allow the electrolyte to be evenly impregnated into the multi-layer braided tube.
[0377] Preparation of the fourth protective layer: The fourth protective layer is woven on the surface of the zinc-air battery unit. An 8-spindle circular knitting machine is used at a speed of 30 r / min to tightly weave 8 PTFE fibers outside the lithium-ion battery unit.
[0378] 2.5 Series and parallel connection and packaging of energy storage units In an inert gas environment, conductive silver glue is used to reinforce the connection points between each electrode and the lead to improve conductivity, and epoxy resin is used to seal the connection points. Finally, the entire composite fiber energy storage device is sealed with a polytetrafluoroethylene (PTFE) heat shrink tube to prevent electrolyte leakage and environmental corrosion.
[0379] 3. Testing and characterization of composite devices 3.1 Voltage and current output test: Test the voltage output changes of each energy storage unit under different series-parallel configurations to verify the voltage superposition effect of the series design and the capacity improvement effect of the parallel design.
[0380] 3.2 Cycle life test: At a charge and discharge rate of 0.1C, the specific capacity of the device was measured to be 310mAh / g. After 5000 cycles at 0.5C, the average capacity retention rate of each unit exceeded 90%.
[0381] 3.3 Safety and mechanical stability test: Under the condition of bending radius of 25mm, 1000 bending tests were carried out, and there was no obvious decline in the performance of each unit, and the average capacity retention rate exceeded 95%.
[0382] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. An energy storage unit having a multi-layer fiber braided tube structure, wherein the multi-layer fiber braided tube structure comprises an inner braided electrode, a middle diaphragm layer and an outer braided electrode; The composition of the inner braided electrode includes a first current collector-active electrode composite fiber and a first support material fiber; the inner braided electrode is a positive electrode or an anode; the chemical composition of the first current collector-active electrode composite fiber includes a first current collector fiber and a first electrode active material; The composition of the middle diaphragm layer includes diaphragm material; The outer braided electrode is composed of a second current collector-active electrode composite fiber and a second support material fiber; the chemical composition of the second current collector-active electrode composite fiber includes a second current collector fiber and a second electrode active material; The energy storage unit further includes an electrolyte, wherein the electrolyte includes solid electrolyte fibers or an electrolyte solution; The diaphragm material includes diaphragm material fibers or layered diaphragm materials; the diaphragm material fibers include at least one of Nafion fibers, polyethylene fibers, polyacrylonitrile fibers, polypropylene fibers, polytetrafluoroethylene fibers, polyimide fibers, polyethersulfone fibers, polyurethane fibers and polytetrafluoroethylene-hexafluoropropylene copolymer fibers; the layered diaphragm material includes a ceramic coated diaphragm, an alumina coated diaphragm or a silica coated diaphragm.
2. The energy storage unit according to claim 1, characterized in that: When the diaphragm material is diaphragm material fiber, the composition of the middle diaphragm layer also includes third support material fiber and / or electrolyte fiber.
3. The energy storage unit according to claim 2, characterized in that: The first current collector fiber and the second current collector fiber independently include at least one of metal fiber, carbon fiber containing a metal coating, and carbon fiber; The first support material fiber, the second support material fiber and the third support material fiber independently include at least one of polytetrafluoroethylene fiber, polyvinylidene fluoride, polyethylene fiber, polyimide fiber, aramid fiber, glass fiber, carbon fiber, polyetheretherketone fiber, fluororubber fiber and nano-ceramic fiber.
4. The energy storage unit according to any one of claims 1 to 3, characterized in that: The energy storage unit also includes a protective layer located on the surface of the outer braided electrode.
5. The energy storage unit according to claim 4, characterized in that: The energy storage unit includes a metal ion battery, a metal air battery, a liquid flow battery, a supercapacitor, a dry cell, a fuel cell, an all-solid-state battery or a redox liquid flow battery; the metal ion battery includes a lithium ion battery, a sodium ion battery, a magnesium ion battery, an aluminum ion battery or a potassium ion battery.
6. The method for preparing the energy storage unit according to any one of claims 1 to 5, comprising the following steps: Performing a first weaving on the raw materials for preparing the inner layer braided electrode to obtain the inner layer braided electrode; The raw materials for preparing the middle diaphragm layer are subjected to a second weaving or winding process on the surface of the inner woven electrode to obtain the middle diaphragm layer; The raw materials for preparing the outer braided electrode are subjected to a third weaving process on the surface of the middle diaphragm layer to form an outer braided electrode, thereby obtaining the energy storage unit; When the electrolyte is a solid electrolyte, solid electrolyte fibers are added during the second weaving or winding process; When the electrolyte is an electrolyte solution, the method further comprises: placing the multi-layer fiber braided tube obtained by the third braiding in the electrolyte solution for immersion or electrophoretic deposition; Alternatively, the multi-layer fiber braided tube obtained by the third braiding is sprayed with an electrolyte solution.
7. A composite fiber energy storage device, characterized in that: It has an overall multi-layer braided tube structure composed of n layers of energy storage units, and a protective layer is arranged between adjacent energy storage units; n is an integer not less than 2; the types of the n layers of energy storage units are the same or different; the n layers of energy storage units are connected in series and / or in parallel; the energy storage unit is the energy storage unit according to any one of claims 1 to 5.
8. The composite fiber energy storage device according to claim 7, characterized in that: The series connection is that the second current collector fiber in the upper layer of energy storage unit is connected in series with the first current collector fiber in the lower layer of energy storage unit; the connection mode of the series connection is circuit connection; The parallel connection is that the first current collector fibers of the energy storage unit are connected in parallel with the first current collector fibers, and the second current collector fibers are connected in parallel with the second current collector fibers; the parallel connection mode is circuit connection; The dynamic switching of different energy storage modes of the composite fiber energy storage device is regulated by a circuit connection mode; the circuit connection mode includes at least one of a switching switch, a dynamic electrode connector and an electronic control unit; the different energy storage modes include at least one of a high voltage mode, a high power mode and a long endurance mode.
9. The method for preparing the composite fiber energy storage device according to claim 7 or 8, comprising the following steps: (1) performing a first weaving on the raw materials for preparing the inner layer braided electrode to obtain the inner layer braided electrode; The raw materials for preparing the middle diaphragm layer are subjected to a second weaving or winding process on the surface of the inner woven electrode to obtain the middle diaphragm layer; The raw materials for preparing the outer braided electrode are braided for the third time on the surface of the middle diaphragm layer to form the outer braided electrode to obtain the first layer of energy storage units, and a protective layer is prepared on the surface of the first layer of energy storage units; When the electrolyte is a solid electrolyte, solid electrolyte fibers are added during the second weaving or winding process; When the electrolyte is an electrolyte solution, the method further comprises: placing the multi-layer fiber braided tube obtained by the third weaving in the electrolyte solution for immersion or electrophoretic deposition; or spraying the multi-layer fiber braided tube obtained by the third weaving with the electrolyte solution; (2) Repeat step (1) n-1 times on the surface of the protective layer to obtain the composite fiber energy storage device.
10. Use of the energy storage unit according to any one of claims 1 to 5 or the composite fiber energy storage device according to claim 7 or 8 in wearable devices, smart textiles or flexible electronics.
Citation Information
Patent Citations
Fiber-like-structured lithium ion battery and preparation method
CN107591559A
Folding-resistant one-dimensional fibrous flexible energy storage device and preparation method thereof
CN109979763A
Preparation method of lithium-sulfur battery diaphragm
CN110911618A
Preparation method of elastic lithium battery with woven structure
CN113161624A
Fiber battery and large-scale preparation method thereof
CN116154325A